Palladium-coated copper bonding wire, method for manufacturing palladium-coated copper bonding wire, wire bonding structure using the same, semiconductor device, and method for manufacturing the same

By forming an alloy layer with high palladium concentration and optimizing the composition of the ball joint on the air-free ball surface, the problem of the unextended bonding life of the palladium-covered copper lead under severe conditions is solved, and high bonding reliability in high temperature and high humidity environments and rounding in narrow-pitch bonding are improved.

CN113748493BActive Publication Date: 2025-03-21TANAKA DENSHI KOGYO KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980091220.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-12
Filing Date
2019-07-04
Publication Date
2025-03-21
Estimated Expiration
2039-07-04

AI Technical Summary

Technical Problem

When used in severe conditions, the bonding life of the existing palladium-covered copper leads has not been extended, and the bonding reliability is reduced in high temperature and high humidity environments, especially in narrow-pitch bonding, the true circularity is difficult to control.

Method used

By forming an alloy layer or enrichment layer with high palladium concentration on the surface of the air-free balloon, the composition of the ball joint is optimized, and a specific palladium covers the copper bonding line structure is adopted, including forming a palladium layer of 1.0% to 4.0% by mass on the copper core material, and containing chalcogen elements, controlling the crystal orientation and the formation of the palladium enrichment region.

Benefits of technology

The bonding reliability of ball welding is significantly improved, especially in high temperature and high humidity environments, which extends the bonding life, and improves the circleability of the first bonding shape in narrow pitch bonding, reducing the occurrence of short circuit failure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113748493B_ABST
    Figure CN113748493B_ABST
Patent Text Reader

Abstract

The Pd-coated Cu bonding wire of the embodiment of the present invention contains 1.0 to 4.0 mass % of Pd and a total of 50 mass ppm or less of S group elements (5.0 to 12.0 mass ppm of S, 5.0 to 20.0 mass ppm of Se, or 15.0 to 50 mass ppm of Te). <100> The orientation ratio is 15% or more, and <111> The orientation ratio was 50% or less. When a free air ball was formed on the wire and the tip portion was analyzed, a Pd-rich region was observed on the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a palladium-coated copper bonding wire suitable for ball bonding between an electrode of a semiconductor element and an external electrode, a method for manufacturing the same, a wire bonding structure using the same, a semiconductor device, and a method for manufacturing the same. Background Art

[0002] Generally speaking, the electrode of the semiconductor element is connected to the external electrode on the semiconductor circuit wiring substrate by wire bonding. The wire bonding has one end connected to the electrode of the semiconductor element and the other end connected to the external electrode. One end is bonded to the electrode of the semiconductor element by a method called ball bonding (first bonding), and the other end is bonded to the external electrode by a method called wedge bonding (second bonding).

[0003] In ball bonding, a molten ball is formed at the tip of a bonding wire, and the bonding wire is connected to, for example, an aluminum electrode surface on a semiconductor element via the molten ball.

[0004] In the formation of the molten ball, first, the front end of the bonding wire is set in the vertical direction, and an arc discharge is formed between the bonding wire and the discharge welding gun by the discharge balling (EFO) method. The discharge current heats and melts the front end of the bonding wire. The molten metal rises in the lead due to its surface tension, forming a true spherical molten ball at the front end of the lead. It solidifies to form a free air ball (FAB). One end of the bonding wire is bonded to the aluminum electrode by crimping the free air ball on the electrode while heating the electrode of the semiconductor element to about 140 to 300°C and applying ultrasonic waves.

[0005] In wire bonding, gold wire with a wire diameter of about 10 to 30 μm is used, but since gold is very expensive, copper wire is used in some places where it can be substituted. However, copper wire is easily oxidized, so in order to prevent oxidation, palladium-coated copper wire with palladium coated on the surface is used.

[0006] However, the palladium-coated copper lead wire has the problem of balancing the bonding stability with the aluminum electrode and the loop stability caused by oxidation of the ball surface. To address this problem, for example, a palladium-coated copper lead wire containing sulfur in the copper core material has been proposed (see, for example, Patent Document 1).

[0007] Although the palladium-coated copper lead has the problem of oxidation of the lead or the free air ball that copper itself has, and the problem of improving the properties that are easily damaged by the coating, it is cheaper than gold. Therefore, the palladium-coated copper lead has rapidly spread in the use of personal computers and their peripheral equipment, communication equipment and other civilian equipment under relatively mild conditions. Furthermore, in recent years, the improvement of palladium-coated copper leads has made progress, and the transition to palladium-coated copper leads for bonding wires used under harsh conditions such as vehicle-mounted equipment has also made progress. Therefore, for palladium-coated copper leads, in order to be suitable for vehicle-mounted equipment, it is required to withstand extremely harsh and drastically changing conditions. Specifically, it is required to withstand a wide range of natural environments or their changes from high temperature and high humidity areas such as tropical places or deserts to cold areas, and from mountainous areas to coastal areas, and then withstand shocks or vibrations caused by road events or traffic events. Furthermore, in recent years, not only the application in the engine room of a car but also the application in semiconductor products carried in an aircraft has been studied. Therefore, regarding bonding reliability, a palladium-coated copper bonding wire that satisfies a higher level of reliability than ever before and can withstand use under conditions ranging from relatively mild conditions in consumer applications to severe conditions is required.

[0008] In the process of developing palladium-coated copper leads that meet such high reliability requirements, attempts have been made to increase the bonding life by forming an alloy layer or enriched layer with a high palladium concentration on the surface of a free air ball (see, for example, Patent Documents 2 and 3).

[0009] Furthermore, in order to improve the formability and bonding properties of the ball portion, the composition near the ball joint portion has been adjusted (see, for example, Patent Document 4).

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2012-156307

[0013] Patent Document 2: International Publication No. 2016 / 189758

[0014] Patent Document 3: Japanese Patent Application Publication No. 2017-92078

[0015] Patent Document 4: Japanese Patent Application Publication No. 2011-146754 Summary of the invention

[0016] Problems to be solved by the invention

[0017] The palladium-coated copper lead increases the palladium concentration on the surface of the free air ball, thereby improving the bonding life compared to conventional leads (leads that are used under relatively mild conditions and do not have a high palladium concentration on the surface of the free air ball). However, it is known that if such palladium-coated copper leads are used under severe conditions, the bonding life is often not that extended.

[0018] The inventors of the present invention presumed that, for the palladium-coated copper lead whose bonding life was not extended, large shrinkage cavities were observed to be generated on the surface of the free air ball, which became a factor that hindered the extension of the bonding life. In other words, it is believed that when the free air ball is bonded to the aluminum electrode in a state with shrinkage cavities in it, a gap is generated in the bonding interface, and the gap becomes a starting point for corrosion, resulting in a reduction in the bonding life.

[0019] The inventors conducted intensive studies on the cause and concluded that a portion of gold or silver plated on the surface of the external electrode adheres to the end of the torn lead after the second bonding, and this gold or silver serves as a starting point for generating shrinkage cavities in the free air ball.

[0020] In addition, with the significant high integration and high density of semiconductor elements in recent years, the requirements for narrow pitch, thin wire, multi-pin / long lead, etc. of wire bonding have become stricter. Among them, the narrowing of pitch has accelerated sharply. As far as the current mass production level is concerned, a 60μm pitch has been achieved, and the development of a 50μm pitch is underway. Furthermore, it is expected that extremely narrow pitches such as 45μm and 40μm will be put into practical use. For extremely narrow pitch bonding, compared with ordinary bonding, a small-diameter ball with a small ball diameter is used in the first bonding part. The narrower the pitch bonding, the more roundness of the first bonding is required. This is because: if the roundness of the first bonding is reduced and the anisotropy is increased, the adjacent wiring contacts and a short circuit defect occurs.

[0021] Furthermore, even if one attempts to control the composition of the ball bonded portion when the palladium-coated copper wire is bonded to the electrode, there is a problem that it is extremely difficult to stably control the composition.

[0022] The present invention is made to solve the above-mentioned problems, and its purpose is to provide a palladium-coated copper bonding wire and a manufacturing method thereof, which can avoid large shrinkage cavities that become a problem on the ball surface during ball formation, can stably maintain the bonding reliability of the ball soldering even in a high temperature and high humidity environment, and can improve the roundness of the first bonding shape even in narrow pitch bonding.

[0023] In addition, the object of the present invention is to provide a semiconductor device that can stably maintain bonding reliability even in a high temperature and high humidity environment and can improve the roundness of the first bonding shape even in narrow pitch bonding, particularly a semiconductor device suitable for QFP (Quad Flat Packaging), BGA (Ball Grid Array), and QFN (Quad For Non-Lead Packaging) packages that can be used in automotive applications and a method for manufacturing the same.

[0024] Means for solving problems

[0025] The palladium-coated copper bonding wire of the present invention has a core material with copper as the main component and a palladium layer on the core material, and contains a chalcogen. The palladium-coated copper bonding wire contains 1.0 mass% to 4.0 mass% of palladium and a total of 50 mass ppm or less of chalcogen (5.0 mass ppm to 12.0 mass ppm of sulfur, 5.0 mass ppm to 20.0 mass ppm of selenium, or 15.0 mass ppm to 50.0 mass ppm of tellurium) relative to the total of copper, palladium and chalcogen. Crystal orientation in the lead length direction in the crystal plane of the cross section of the palladium-coated copper bonding wire <hkl>Among them, <100> The total of the orientation ratios is 15% or more, and <111> The orientation ratio is 50% or less. <100> and <111> The orientation includes an orientation with an angle difference of less than 15° relative to the length direction of the lead wire. When a free air ball is formed on the palladium-coated copper bonding wire, a palladium-enriched region containing 6.5 atomic % to 30.0 atomic % of palladium relative to the total of copper and palladium is observed within a depth range of 5.0 nm to 100.0 nm from the surface of the front end portion of the free air ball.

[0026] The palladium-coated copper bonding wire of the present invention preferably contains a total of 1 mass ppm to 3 mass % of one or more trace elements selected from P, Au, Pd, Pt, Ni, Ag, Rh, In, Ga and Fe in the core material relative to the entire core material. In addition, as trace elements, when containing one or more selected from Au, Pd, Pt, Ni and Rh, their contents are preferably 0.05 mass % to 3 mass %, when containing one or more selected from In and Ga, their contents are preferably 0.01 mass % to 0.7 mass %, when containing P, their contents are preferably 5 mass ppm to 500 mass ppm, and when containing one or more selected from Ag and Fe, their contents are preferably 1 mass ppm to 100 mass ppm.

[0027] The palladium-coated copper bonding wire of the present invention preferably has a palladium concentration derived from the palladium layer of 1.0 mass % to 2.5 mass % relative to the total of copper, palladium, and chalcogenide.

[0028] The wire diameter of the palladium-coated copper bonding wire of the present invention is preferably 10 μm to 25 μm.

[0029] In the palladium-coated copper bonding wire of the present invention, the formation conditions of the free air ball when detecting the palladium-rich region are preferably a discharge current value of 65 mA, a ball diameter of 1.8 times the lead wire diameter, and the presence of a mixed gas of nitrogen and hydrogen.

[0030] In the palladium-coated copper bonding wire of the present invention, the palladium concentration in the palladium-rich region is preferably such that the acceleration voltage of the primary electron beam is 10 kV and the measurement area calculated from the setting value is 15 μm. 2 ~20μm 2 , the concentration when the acceleration voltage of argon ion sputtering is 1 kV and the sputtering rate is 2.5 nm / min (SiO2 conversion).

[0031] The palladium-coated copper bonding wire of the present invention preferably has a gold layer on the palladium layer.

[0032] The method for manufacturing a palladium-coated copper bonding wire of the present invention manufactures a palladium-coated copper bonding wire having a core material with copper as a main component and a palladium layer on the core material and containing a chalcogen element. The palladium-coated copper bonding wire contains 1.0 mass% to 4.0 mass% of palladium and a total of 50 mass ppm or less of chalcogen elements (5.0 mass ppm to 12.0 mass ppm of sulfur (S), 5.0 mass ppm to 20.0 mass ppm of selenium (Se), or 15.0 mass ppm to 50.0 mass ppm of tellurium (Te)) relative to the total of copper, palladium and chalcogen elements. The manufacturing method has the following steps: a step of preparing a copper wire having copper as a main component; a step of forming a palladium layer containing the chalcogen element on the surface of the copper wire; a step of stretching the copper wire having the palladium layer formed thereon by 50% or more; and a step of heat-treating the copper wire so that the elongation after the stretching becomes 5% to 15%.

[0033] The wire bonding structure of the present invention comprises an electrode of a semiconductor chip comprising aluminum, a bonding wire, and a ball bonding portion between the electrode and the bonding wire. The bonding wire is a palladium-coated copper bonding wire having a core material with copper as a main component and a palladium layer on the core material, and containing a chalcogen element. The palladium-coated copper bonding wire comprises 1.0 mass % to 4.0 mass % of palladium, and a total of 50 mass ppm or less of chalcogen elements (5.0 mass ppm to 12.0 mass ppm of sulfur (S), 5.0 mass ppm to 20.0 mass ppm of selenium (Se), or 15.0 mass ppm to 50.0 mass ppm of tellurium (Te)) relative to the total of copper, palladium and chalcogen elements. Crystal orientation in the length direction of the lead in the crystal plane of the cross section of the palladium-coated copper bonding wire <hkl>Among them, <100> The orientation ratio is 15% or more, and <111> The orientation ratio is 50% or less. <100> and <111> The orientation includes an orientation with an angle difference of less than 15° relative to the length direction of the lead wire. If a lead bonding structure is prepared in which the palladium-coated copper bonding wire is ball-bonded to an aluminum electrode, a palladium-enriched bonding region having a palladium concentration of 2 mass % or more relative to the total of aluminum, palladium and copper is provided near the bonding surface of the ball bonding on the aluminum electrode.

[0034] In the wire bonding structure of the present invention, the palladium-enriched bonding region is preferably arranged on a line parallel to the length direction of the wire passing through at least one eighth of the distance between both ends of the maximum width of the ball bond.

[0035] In the wire bonding structure of the present invention, the occupancy rate of the palladium-rich bonding region near the bonding surface is preferably 25% or more.

[0036] The semiconductor device of the present invention comprises a semiconductor chip, an aluminum electrode containing aluminum disposed on the semiconductor chip, an external electrode disposed outside the semiconductor chip and coated with gold or silver, and a bonding wire connecting the aluminum electrode to the surface of the external electrode. The bonding wire is made of a copper wire coated with palladium. The wire bonding structure of the present invention is provided near the bonding surface between the aluminum electrode and the bonding wire.

[0037] The semiconductor device of the present invention comprises a semiconductor chip, an aluminum electrode containing aluminum disposed on the semiconductor chip, an external electrode disposed outside the semiconductor chip and coated with gold or silver, and a bonding wire connecting the aluminum electrode to the surface of the external electrode. The bonding wire is made of the palladium-coated copper bonding wire of the present invention.

[0038] The semiconductor device of the present invention is preferably a QFP (Quad Flat Packaging), a BGA (Ball grid array) or a QFN (Quad For Non-Lead Packaging). In addition, the semiconductor device of the present invention is preferably used in vehicles.

[0039] The wire bonding structure of the present invention can be formed by forming an air-free ball using the palladium-coated copper bonding wire of the above-mentioned structure and bonding the ball to an electrode containing aluminum of a semiconductor chip. At this time, a palladium-enriched bonding area of ​​the above-mentioned specific composition is formed near the bonding surface of the ball bonding. Therefore, the bonding reliability of the first bonding (ball bonding) can be significantly improved. In other words, when the palladium-coated copper wire of the above-mentioned structure is subjected to a bonding test to make a wire bonding structure by the above-mentioned ball bonding, a palladium-enriched bonding area of ​​the above-mentioned specific composition is formed near the bonding surface of the ball bonding. As a result, the bonding reliability of the first bonding (ball bonding) can be significantly improved.

[0040] The method for manufacturing a semiconductor device of the present invention manufactures a semiconductor device having a semiconductor chip, an aluminum electrode disposed on the semiconductor chip and containing aluminum, an external electrode disposed outside the semiconductor chip and covered with gold or silver, and a bonding wire connecting the aluminum electrode to the surface of the external electrode. The bonding wire is a palladium-coated copper bonding wire having a core material with copper as a main component and a palladium layer on the core material, and containing a chalcogen element. The palladium-coated copper bonding wire contains 1.0 mass% to 4.0 mass% of palladium, and a total of 50 mass ppm or less of chalcogen elements (5.0 mass ppm to 12.0 mass ppm of sulfur, 5.0 mass ppm to 20.0 mass ppm of selenium, or 15.0 mass ppm to 50.0 mass ppm of tellurium) relative to the total of copper, palladium and chalcogen elements. Crystal orientation in the lead length direction in the crystal plane of the cross section of the palladium-coated copper bonding wire <hkl>Among them, <100> The total of the orientation ratios is 15% or more, and <111> The orientation ratio is 50% or less. <100> and <111> The orientation includes an orientation with an angle difference of less than 15° relative to the length direction of the lead wire. When a free air ball is formed on the palladium-coated copper bonding wire, a palladium-enriched region containing 6.5 atomic % to 30.0 atomic % of palladium relative to the total of copper and palladium is observed within a depth range of 5.0 nm to 100.0 nm from the surface of the front end portion of the free air ball. The manufacturing method includes the following steps: a step of forming a free air ball at the front end of the palladium-coated copper bonding wire; a step of ball-bonding the palladium-coated copper bonding wire to the aluminum electrode through the free air ball; and a step of bonding a portion separated from the free air ball by the length of the palladium-coated copper bonding wire to the surface of the external electrode.

[0041] In this specification, the symbol "to" indicates a numerical range including the numerical values ​​around it. Chalcogen elements are at least one of sulfur (S), selenium (Se) and tellurium (Te). In addition, unless otherwise specified, <111> Crystal orientation ratio ( <111> Orientation ratio) refers to the crystal orientation along the length of the lead <hkl>This includes orientation ratios where the angle difference with respect to the lead length direction is within 15°. <100> Crystal orientation ratio ( <100> The term "orientation ratio" also refers to an orientation ratio including an angle difference within 15°.

[0042] Effects of the Invention

[0043] According to the palladium-coated copper bonding wire and the wire bonding structure of the present invention, large shrinkage cavities that may be a problem are not generated on the ball surface during ball formation, and the roundness of the first bonding shape can be improved even in narrow pitch bonding. Therefore, when used for ball bonding, the occurrence of short circuit failures can be suppressed even in narrow pitch bonding, and excellent bonding reliability can be stably maintained for a long time even in a high temperature and high humidity environment.

[0044] Furthermore, according to the semiconductor device and the method for manufacturing the same of the present invention, the occurrence of short-circuit failures in narrow-pitch bonding can be suppressed, and excellent bonding reliability can be stably maintained for a long period of time even in a high-temperature, high-humidity environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a diagram for explaining the formation location of the palladium-enriched junction region.

[0046] Figure 2 This is a photograph of a free air ball having small shrinkage cavities that are not problematic and that were observed in Examples.

[0047] Figure 3 This is a photograph of a free air ball having a large shrinkage cavity observed in a comparative example.

[0048] Figure 4 : is an Auger (FE-AES) analysis curve of the front end surface of the free air ball of the example.

[0049] Figure 5 It is a field emission scanning electron microscope / energy dispersive X-ray spectroscopy (FE-SEM / EDX) curve of the junction structure of the example.

[0050] Figure 6 FE-SEM / EDX curves of other parts of the bonding structure of the example.

[0051] Figure 7 It is a schematic diagram showing a semiconductor device according to an embodiment.

[0052] Figure 8 This is an electron probe microanalyzer (EPMA) image of the bonding structure of the example.

[0053] Fig. 9 This is an EPMA image of a bonding structure in which no palladium exists near the bonding surface. DETAILED DESCRIPTION

[0054] Hereinafter, embodiments of the present invention will be described in detail.

[0055] The palladium (Pd) coated copper bonding wire of this embodiment has a core material with copper as the main component and a palladium layer on the core material. The palladium coated copper bonding wire contains a chalcogen element, and the concentration of palladium is 1.0 to 4.0 mass % relative to the total of copper, palladium and chalcogen elements. When two or more chalcogen elements are contained, the total concentration is 50 mass ppm or less. Crystal orientation in the crystal plane of the cross section of the core material of the palladium coated copper bonding wire in the lead length direction <hkl>Among them, <100> The orientation ratio is 15% or more, and <111> The orientation ratio is 50% or less. <100> Orientation and <111> The orientation includes an orientation in which the angle difference with respect to the lead length direction is within 15°.

[0056] In the palladium-coated copper bonding wire of the present embodiment, the sulfur concentration in the chalcogen element is 5 to 12 mass ppm, the selenium concentration is 5 to 20 mass ppm, or the tellurium concentration is 15 to 50 mass ppm.

[0057] The properties of the palladium-coated copper bonding wire of the present embodiment can be confirmed by analyzing the front end of the free air ball made using the same (wire analysis with FAB). That is, the palladium-coated copper bonding wire of the present embodiment is formed into a free air ball (FAB) by the above-mentioned composition and the front end portion thereof is analyzed. In the range of 5.0nm to 100.0nm in the depth direction from the surface of the front end portion of the FAB, a palladium-enriched region containing 6.5 to 30.0 atomic % palladium relative to the total of copper and palladium is observed. In addition, when the palladium-coated copper bonding wire of the present embodiment is ball-bonded to form a bonding structure by the palladium-coated copper bonding wire of the above-mentioned composition, a palladium-enriched bonding region (a region where the mass ratio of palladium to the total of palladium, copper and aluminum is 2.0 mass % or more, preferably 5.0 mass % or more) is formed near the bonding surface, that is, in the region where aluminum and palladium coexist. The ball bonding conditions and analysis conditions will be described below.

[0058] In other words, whether the palladium-coated copper lead exhibits the above-mentioned long-term high reliability can be determined by preparing the palladium-coated copper lead, using it to form a free air ball (FAB) under the above-mentioned conditions, analyzing the front end portion thereof without performing the first bonding, and whether the above-mentioned palladium-enriched region is observed. That is, the prepared palladium-coated copper lead contains palladium and chalcogenide elements at the above-mentioned prescribed concentrations, and when the lead with FAB is used to perform the lead analysis, if a palladium-enriched region is observed at the front end portion of the FAB, it can be determined that the prepared palladium-coated copper lead contains chalcogenide elements in the palladium layer, and satisfies the configuration of the palladium-coated copper bonding wire of the present embodiment that exhibits long-term high reliability.

[0059] In the palladium-coated copper bonding wire of the present embodiment, the copper core material may also contain palladium. When the palladium-coated copper bonding wire has no other layers on the palladium layer and the copper core material contains palladium, the palladium concentration of the lead as a whole is the sum of the palladium concentration derived from the palladium layer and the palladium concentration derived from the copper core material. When there is no other layer on the palladium layer, the concentration of palladium derived from the palladium layer is preferably 1.0 to 2.5% by mass relative to the sum of copper, palladium and chalcogen elements of the lead as a whole. When the palladium-coated copper bonding wire of the present embodiment has other layers on the palladium layer, the palladium that permeates from the palladium layer into the other layers by diffusion or the like can also be regarded as the palladium derived from the palladium layer to obtain the palladium concentration.

[0060] The palladium (Pd) coated copper bonding wire of this embodiment can improve the reliability of ball bonding by having a palladium concentration of 1.0 mass% or more and containing a predetermined amount of each chalcogenide element, so that excellent ball bonding can be maintained for a long time even under high temperature and high humidity. The palladium concentration is 4.0 mass% or less, and in particular, the palladium concentration of the palladium layer is 2.5 mass% or less, which can suppress the generation of shrinkage cavities in the free air ball (FAB). In this way, by having a palladium concentration of 1.0 to 4.0 mass% and containing a predetermined amount of each chalcogenide element, it is possible to achieve both high reliability of ball bonding and suppression of shrinkage cavities when forming a free air ball.

[0061] From the viewpoint of obtaining high reliability of ball bonding, the concentration of palladium derived from the palladium layer is preferably 1.3 mass % or more, and from the viewpoint of suppressing the generation of shrinkage cavities, the concentration of palladium derived from the palladium layer is preferably 2.3 mass % or less.

[0062] The palladium concentration derived from the palladium layer can be calculated by measuring the palladium concentration of the entire lead and the palladium concentration in the copper core material, respectively. Specifically, it can be analyzed by secondary ion mass analysis (SIMS) as follows. First, the lead to be measured is pressed to make it flat. A SIMS analysis device (for example, an IMS-7f secondary ion mass spectrometer made by CAMECA) is used to measure the concentration of palladium in the copper (Cu) core material. The palladium layer on the surface of the flattened lead is removed by sputtering in the above-mentioned analysis device to expose the copper. In order to expose the copper (Cu), for example, for a lead with a wire diameter of 10μm to 30μm, at least 0.5μm is sputtered from the surface in terms of palladium (Pd) conversion. After removing the palladium layer, SIMS analysis is started and analyzed to 2.0μm in the depth direction. From the start point of the analysis to the end point of the analysis (depth 2.0μm), for example, more than 100 points are measured, and the average concentration of the 100 points is calculated. Regarding the analysis conditions, for example, as the setting conditions of the SIMS apparatus, the primary ion species is Cs + , the primary ion acceleration voltage is 15.0keV, the primary ion irradiation area is about 30μm×30μm, and the analysis area is about 12μm×12μm. SIMS analysis uses a mass spectrometer to detect Cs + The elemental analysis is performed on the secondary ions emitted by the primary ions through sputtering. However, the palladium concentration can be obtained by using the measured secondary ion intensity of palladium (Pd) and converting the concentration of a copper (Cu) wire with a known palladium (Pd) concentration as a standard sample.

[0063] Chalcogenides are mainly contained in the palladium layer. However, since the amount of chalcogenides is extremely small, it is currently impossible to accurately measure the location and concentration of the chalcogenides by various analytical methods, especially in a structure where the palladium layer is very thin. Therefore, the amount of the chalcogenides is set to the above range relative to the entire palladium-coated copper bonding wire.

[0064] Crystal orientation of the palladium-coated copper bonding wire in the lead length direction in the crystal plane of the cross section of the present embodiment <hkl>Among them, <100> The ratio of orientation (including orientation within an angle difference of 15° with respect to the lead length direction) is 15% or more, and <111> The ratio of orientation (including orientation with an angle difference of less than 15° relative to the length direction of the lead) is less than 50%. As a result, the shape of the ball joint (first joint) portion becomes an ellipse or other irregular shapes that deviate from the true circle, and the ball joint portion can be stably close to the true circle. If the true roundness is good, it becomes beneficial to the small-diameter ball of the air-free ball and the first joint, and the manufacturing management of the joint process becomes easy. For example, in the case of joining small-diameter balls with a ratio of the air-free ball diameter / wire diameter in the range of 1.5 to 1.7, the true roundness of the ball joint portion is stably improved. Therefore, even in a narrow pitch joint with an electrode spacing of, for example, less than 40μm, short circuit failure will not occur, and it becomes easy to maintain high reliability.

[0065] Furthermore, in order to improve the roundness of the ball bond, the crystal orientation in the lead length direction in the crystal plane of the lead cross section is <hkl>Among them, <100> The orientation ratio is preferably 30% or more. <111> The orientation ratio is preferably 40% or less. <100> The upper limit of the orientation ratio and <111> The lower limit of the orientation ratio is not particularly limited, but is considered to be easier to control the crystal orientation during the production of the palladium-coated copper bonding wire. <100> The orientation ratio is preferably 85% or less. <111> The orientation ratio is preferably 15% or more. <111> + <100> The total of the orientation ratios is more preferably 30% or more, and more preferably 90% or less. Within this range, the circularity of bonding can be further improved.

[0066] Compared with single-layer leads, the ball joints with covered leads are more likely to have irregular shapes, but in the previous joint process when the distance (pitch) between electrodes exceeds about 60μm, strict management is not required. However, the smaller the ball diameter, the easier it is for the shape of the ball joint to deviate from the true circle and become irregular, and the narrower the pitch, the easier it is for a part of the ball joint to protrude from the electrode, or for the ball joint to contact the adjacent electrode and cause a short circuit.

[0067] The inventors studied the countermeasures for short circuit failure caused by deterioration of the roundness of the ball joint in narrow pitch bonding, and found that by controlling the crystal orientation of the crystal plane of the lead cross section, the deformation behavior of the airless ball during the first bonding and the deformation behavior caused by ultrasonic wave application was investigated. <111> and <100> The crystal orientation ratio can improve the roundness of the ball joint and reduce the irregular shape. In particular, it is found that the palladium-coated copper bonding wire with the above composition can improve the roundness even when bonding small-diameter balls with a ratio of 1.5 to 1.7 of free-air ball diameter / lead wire diameter, and can reduce short-circuit defects in narrow-pitch bonding.

[0068] This is presumably based on the following reasons. According to the palladium-coated copper bonding wire of this embodiment, a palladium-enriched region containing palladium at a predetermined concentration is formed in a layer near the surface of the airless ball formed during the first bonding. It is believed that in the extremely short period of time from the melting of the lead wire by arc discharge to solidification to form a molten ball until the ball is bonded, the structure inside the palladium-enriched region on the ball surface forms a uniform structure, making the deformation caused by the load of the bonding device or the application of ultrasonic waves more uniform. Therefore, it is believed that the true roundness is improved even in the first bonding with a narrow pitch.

[0069] The crystal structure of the crystal surface of the wire cross section can be measured using the Electron Back Scattering Pattern (EBSP) method. By measuring the texture using the EBSP method, the texture of the cross section can be measured with good accuracy and sufficient reproducibility even for thin wires such as bonding wires.

[0070] When measuring the crystal orientation of the lead cross section, any one of the vertical cross section in the lead length direction or the parallel cross section parallel to the lead length direction and near the center of the lead can be measured. With regard to the EBSP method, it is usually difficult to measure the crystal orientation with high precision when the sample is concave-convex and the curved surface is large. Therefore, in order to observe the lead cross section by EBSP, it is useful to process the surface of the cross section smoothly. As a method for processing the surface of the cross section smoothly, there are mechanical grinding, chemical grinding, FIB processing method, etc. According to these methods, the residual strain on the surface of the cross section can be removed to obtain a smooth surface. In addition, for the measurement of crystal orientation, a cross section perpendicular to the lead length direction is preferred because it is easy to obtain a smooth cross section.

[0071] If the sample pretreatment is optimized as described above, the crystal orientation of the lead cross section can be measured and analyzed with high accuracy by the EBSP method. The crystal orientation can be measured at three or more different locations to obtain average information that takes into account the variation.

[0072] In addition, in the EBSP method, standard data (standard pattern file) of a material having the same composition as the structure of the measurement object is used. However, in the palladium-coated copper bonding wire of the present embodiment, since the concentration of chalcogen elements, the concentration of palladium, and the concentration of trace elements in copper are extremely small relative to the entire lead, when the crystal structure of the lead cross section is measured by the EBSP method, data of pure copper can also be used as standard data.

[0073] Next, other configurations of the palladium-coated copper bonding wire of this embodiment are described. The wire diameter of the palladium-coated copper bonding wire of this embodiment is usually 10 to 30 μm, preferably 25 μm or less. The palladium-coated copper bonding wire with a small wire diameter is more suitable for narrow pitch bonding.

[0074] The core material in the palladium-coated copper bonding wire of this embodiment is copper or a copper alloy composed of copper as the main component. The main component here means the central component in terms of quantity or characteristics, and if it is the content, it is at least 50.0% by mass. The characteristics of the main component are the characteristics required for its composition, for example, in the case of a copper core material, the mechanical properties such as the breaking force or elongation of the lead. The main component can be called, for example, a component that centrally affects such characteristics.

[0075] In addition to copper (Cu), the copper core material may also contain trace elements such as inevitable impurities and additive elements. The additive elements are generally elements added in trace amounts for the purpose of improving the oxidation resistance, toughness and other characteristics of the palladium-coated copper bonding wire. Such trace elements are, for example, phosphorus (P), gold (Au), platinum (Pt), Pd (palladium), nickel (Ni), silver (Ag), rhodium (Rh), indium (In), gallium (Ga), iron (Fe), etc. By including trace elements in the copper core material, the reliability of the first bonding can be further improved, and the roundness of the ball bonding portion of the first bonding can be improved. It is believed that the core material containing the above-mentioned trace elements that contribute to the high reliability of the first bonding becomes moderately hard compared to pure copper, so the hardness of the airless ball is slightly harder than that of pure copper, and the deformation of the airless ball caused by the crimping load and ultrasonic application during the first bonding becomes more uniform, so the roundness of the ball bonding portion can be improved. The short circuit defect of the narrow pitch bonding can be suppressed by improving the roundness of the ball bonding portion. In the case where the copper core material contains trace elements, the total amount thereof is preferably 1 mass ppm or more relative to the entire core material. The proportion of trace elements is preferably 3.0 mass % or less. If it is within this range, bonding reliability is obtained, and the increase in cost is suppressed, and the wire drawing processability of the good lead can be maintained, and the increase in the resistivity of the lead can be suppressed. In addition, it becomes difficult to cause chip damage during ball bonding. The proportion of trace elements is more preferably 2.0 mass % or less, and more preferably 1.5 mass % or less.

[0076] Specifically, when the copper core material contains one or more selected from Au, Pt, Pd, Ni and Rh as trace elements, the content ratio relative to the whole core material is preferably 0.05% by mass to 3.0% by mass, more preferably 0.1% by mass to 2.0% by mass, and further preferably 0.2% by mass to 1.0% by mass. In addition, when the copper core material contains Ni among Au, Pt, Pd, Ni and Rh as trace elements, the content ratio relative to the whole core material is preferably 0.1% by mass to 2.0% by mass, and more preferably 0.3% by mass to 1.0% by mass.

[0077] When the copper core material contains one or more of In and Ga as trace elements, the amount thereof is preferably 0.01 mass % to 0.7 mass %, more preferably 0.05 mass % to 0.6 mass %, and further preferably 0.1 mass % to 0.5 mass %. When the copper core material contains P as a trace element, it is preferably 5 mass ppm to 500 mass ppm, more preferably 20 mass ppm to 400 mass ppm, and further preferably 50 mass ppm to 250 mass ppm. When the copper core material contains one or more of Ag and Fe as trace elements, the amount thereof is preferably 1 mass ppm to 100 mass ppm, more preferably 3 mass ppm to 60 mass ppm, and further preferably 5 mass ppm to 30 mass ppm.

[0078] The content ratio of trace elements in copper or elements contained in the lead is generally measured by chemical analysis such as inductively coupled plasma (ICP) emission spectrometry, but is not limited thereto. For example, the content ratio of metal elements in the copper core material can be measured by SIMS analysis in the same manner as palladium in the copper core material.

[0079] The palladium layer can be analyzed as a region from the position where the ratio of palladium to the total of copper and palladium becomes 50.0 atomic % to the surface of the palladium layer in the Auger (FE-AES) analysis curve in the depth direction from the surface of the lead. The position where the ratio of palladium becomes 50.0 atomic % is the boundary between the copper core material and the palladium layer. In the case where it is difficult to clearly determine the thickness of the palladium layer and the existence ratio of palladium in a specific position by FE-AES analysis because the palladium layer is thin, the FE-AES analysis can also be further appropriately combined with analysis using transmission electron microscopy / energy dispersive X-ray spectroscopy (TEM / EDX), analysis using spherical aberration correction transmission electron microscopy / energy dispersive X-ray spectroscopy (STEM / EDX), atomic number contrast imaging (HAADF image), etc.

[0080] The thickness of the palladium layer also varies depending on the wire diameter of the palladium-coated copper bonding wire, but for a wire diameter of 10 μm to 30 μm, it is preferably 0.020 μm to 0.150 μm, and more preferably 0.030 μm to 0.130 μm. This is because when the thickness of the palladium layer is uniform within the above range, the quality of loop characteristics such as the resistance to tilting during bonding of the bonding wire and the stability of the loop height are improved. As a method for measuring the thickness of the palladium layer, the above-mentioned FE-AES analysis can be used. As described above, in order to improve the measurement accuracy, analysis using TEM / EDX, analysis using STEM / EDX, HAADF imaging, etc. can also be appropriately used in combination.

[0081] When the palladium-coated copper bonding wire of the present embodiment contains a chalcogen (one or more of sulfur, selenium and tellurium) and contains two or more chalcogens, the total concentration of the chalcogen in the entire lead is 50.0 mass ppm or less. The total concentration of the chalcogen in the entire lead is preferably 5.0 mass ppm or more, so that the reliability of ball bonding is easily obtained. From the perspective of the reliability of ball bonding, the concentration of the chalcogen in the entire lead is preferably 6.0 mass ppm or more. In addition, if the chalcogen concentration exceeds 50.0 mass ppm, the palladium layer becomes brittle, cracks occur in the palladium layer during wire drawing, or the cracks become the starting point and the lead breaks or the wire drawing processability deteriorates. In order to improve the wire drawing processability, the chalcogen concentration is preferably 45.0 mass ppm or less, and more preferably 41.0 mass ppm or less.

[0082] In the palladium-coated copper bonding wire of the present embodiment, the sulfur (S) concentration of the above-mentioned chalcogen elements is 5.0 mass ppm or more of the entire lead, preferably 6.0 mass ppm or more. The sulfur (S) concentration is 5.0 mass ppm or more, which can improve the reliability of ball bonding. On the other hand, the sulfur (S) concentration is 12.0 mass ppm or less of the entire lead. If it exceeds this, the palladium layer becomes brittle, cracks occur in the palladium layer, or the cracks become the starting point and the lead breaks or the wire drawing processability deteriorates. The sulfur (S) concentration is preferably 10.0 mass ppm or less of the entire lead.

[0083] In addition, the selenium (Se) concentration is 5.0 mass ppm or more of the entire lead, preferably 6.0 mass ppm or more, and more preferably 8.0 mass ppm or more. By having a selenium (Se) concentration of 5.0 mass ppm or more, the reliability of ball bonding can be improved. On the other hand, the selenium (Se) concentration is 20.0 mass ppm or less of the entire lead. If it exceeds this, the palladium layer becomes brittle, cracks occur in the palladium layer, or the cracks become the starting point and the lead breaks or the wire drawing processability deteriorates. The selenium (Se) concentration is preferably 15.0 mass ppm or less of the entire lead.

[0084] In addition, the tellurium (Te) concentration is 15.0 mass ppm or more of the entire lead, and more preferably 16.0 mass ppm or more. By setting the tellurium (Te) concentration to 15.0 mass ppm or more, the reliability of ball bonding can be improved. On the other hand, the tellurium (Te) concentration is preferably 50.0 mass ppm or less of the entire lead. If it exceeds this, the palladium layer becomes brittle, cracks occur in the palladium layer, or the cracks become the starting point and the lead breaks or the wire drawing processability deteriorates. The tellurium (Te) concentration is preferably 45.0 mass ppm or less of the entire lead, and more preferably 41.0 mass ppm or less.

[0085] The palladium-coated copper bonding wire used in this embodiment may contain only one chalcogen element or two or more chalcogen elements as long as the total chalcogen element concentration is within the range of 50 mass ppm or less and any one of sulfur, selenium and tellurium satisfies the above concentration range. As the palladium-coated copper bonding wire contains each chalcogen element at the above concentration, it has the characteristic of forming a palladium-rich region on the surface of the front end of the free air ball, and the above palladium-rich bonding region is easily and stably formed in the ball bonding portion regardless of the ball forming conditions, and the bonding reliability can be significantly improved.

[0086] The palladium-coated copper bonding wire of this embodiment may also have a second layer formed of a metal other than palladium on the palladium layer. The metal of the second layer may be a pure metal or an alloy formed by mixing two or more metals. In the case where the palladium-coated copper bonding wire has a second layer on the palladium layer, the boundary between the palladium layer and the second layer may be measured as a portion where the concentration of the main component metal of the second layer becomes 50.0% relative to the maximum concentration. In the case where there is a third layer or a fourth layer on the surface of the second layer, the above analysis may also be performed.

[0087] The palladium-coated copper bonding wire of the present embodiment preferably has a gold layer as a layer other than the palladium layer in the outermost layer. The palladium-coated copper lead of the present embodiment can improve the bondability of the second bond and reduce the die wear during the wire drawing process by having a gold layer. The gold layer is a layer formed with gold as the main component. As long as the gold layer is formed over the surface of the palladium layer, a part of it may be interrupted, or palladium may be contained in the gold layer. In the case where palladium is contained in the gold layer, the palladium concentration may be uniform in the thickness direction, or it may have a concentration gradient that decays toward the surface. In addition, in the case where the gold layer is composed of an alloy formed by mixing two or more metals, the gold layer may contain silver, copper, etc. in addition to palladium and gold as long as the effect of the present invention is not impaired. In this case, the amount of metal elements other than palladium in the gold layer is, for example, less than 50.0% by mass.

[0088] In the case where the palladium-coated copper bonding wire of the present embodiment has a gold layer, the concentration of gold derived from the gold layer in the entire lead is preferably 0.01 mass % or more, and more preferably 0.05 mass % or more. If the concentration of gold derived from the gold layer is 0.01 mass % or more, the second bonding property is likely to become good, and the die wear during wire drawing is likely to be reduced. The concentration of gold derived from the gold layer in the entire lead is preferably 0.20 mass % or less, and more preferably 0.15 mass % or less. If the concentration of gold derived from the gold layer is 0.20 mass % or less, it is not easy to adversely affect the performance of the lead, and it is not easy to damage the sphericity of the airless ball. It should be noted that when gold is contained in the copper core material, the concentration of gold as the entire lead is the sum of the concentration of gold derived from the above-mentioned gold layer and the concentration of gold in the copper core material. Therefore, when measuring the gold concentration of the gold layer, the gold concentration of the entire lead and the gold concentration in the copper core material can be measured separately, and the gold concentration of the gold layer can be calculated using these. The gold concentration of the gold layer can be specifically measured by SIMS analysis in the same way as the palladium concentration of the palladium layer.

[0089] The thickness of the gold layer also varies depending on the wire diameter of the palladium-coated copper bonding wire, but is preferably less than 8 nm, and more preferably less than 5 nm. If the thickness of the gold layer is less than 8 nm, even in the case of a gold layer, the true sphericity of the airless ball will not be damaged, and it is easy to maintain the high reliability of the ball bonding. The lower limit of the thickness of the gold layer is not particularly limited, but it is sufficient as long as the average film thickness converted by the concentration described later is more than 1 nm. As a method for measuring the thickness of the gold layer, FE-AES analysis can be used in the same way as the palladium layer.

[0090] It should be noted that if the concentration of gold in the entire lead is within the above-mentioned preferred range, the thickness of the gold layer becomes significantly thinner. In the case where the thickness of the gold layer becomes significantly thinner, the current situation is that it is difficult to accurately measure the thickness of the gold layer by general measurement methods. Therefore, in the case where the thickness of the gold layer becomes significantly thinner, the thickness of the gold layer can be evaluated by converting the average film thickness calculated using the concentration of gold in the entire lead and the lead wire diameter. The following method is used to convert the average film thickness into gold: the mass of gold per unit length is calculated from the gold concentration and the specific gravity of gold, and the film thickness is calculated assuming that the cross-section of the lead is a true circle and that gold is uniformly present on the outermost surface; or the following method is used: the thickness of the gold coating measured in terms of the plated wire diameter (the design value can be used) and the final wire diameter are used for proportional calculation.

[0091] (Analysis of Free Air Ball (FAB))

[0092] Next, the analysis of the free air ball is described. As described above, when the palladium-coated copper bonding wire of the present embodiment is subjected to the lead analysis with FAB (i.e., when the free air ball is formed using the palladium-coated copper bonding wire of the present embodiment, and the front end portion is analyzed without performing the first bonding), a palladium-rich region containing 6.5 to 30.0 atomic % of palladium relative to the total of copper and palladium is observed within a depth range of 5.0 nm to 100.0 nm from the surface of the front end portion of the free air ball. The palladium-coated copper bonding wire of the present embodiment contains palladium and chalcogenide elements at specific concentrations of the present embodiment, and stably forms a palladium-rich region near the front end surface of the free air ball, thereby suppressing the generation of large shrinkage cavities that are problematic and hinder the long-term maintenance of the bonding reliability of the first bonding.

[0093] The conditions for forming the free air ball in the lead wire analysis with FAB are the same as those used in the usual first bonding. Specifically, for example, when the wire diameter of the palladium-coated copper bonding wire is 10 to 30 μm, the arc discharge conditions are set so that the discharge current value becomes 30 to 90 mA and the free air ball diameter becomes more than 1.7 times and less than 2.3 times the wire diameter of the lead wire. The bonder device can use commercially available products such as the bonder device made by K&SInc (fully automatic Cu wire bonder; IConn ProCu PLUS). When using this bonder device, as the settings of the device, it is preferred that the discharge time is 50 to 1000 μs, the EFO-Gap is 25 to 45 mil (about 635 to 1143 μm), and the tail length is 6 to 12 mil (about 152 to 305 μm). When using other bonders other than this bonder device, as long as the conditions are the same as those above, for example, the conditions that the free air ball diameter becomes the same size as those above will suffice. In addition, in order to set the lead tip to a mixed gas atmosphere of nitrogen and hydrogen or a nitrogen atmosphere, the above-mentioned gas is blown at a gas flow rate of 0.2 to 0.8 L / min, preferably 0.3 to 0.6 L / min. The gas for forming the free air ball is preferably a mixed gas of 95.0 volume % nitrogen and 5.0 volume % hydrogen, and the free air ball diameter can be within the above range as a target value.

[0094] When observing whether a palladium-enriched region is formed for a predetermined lead, as a representative of the above range, the above enriched region can also be measured by a free air ball formed in the presence of a mixed gas of nitrogen and hydrogen with a discharge current value of 65 mA and a ball diameter of 1.8 times the lead wire diameter. The ball diameter is a target value or a measured value, but the measured value is preferred. In addition, as a generally assumed error range, the free air ball diameter during analysis can be in the range of 1.8±0.05 times the lead wire diameter.

[0095] If the palladium-coated copper bonding wire of the present embodiment is used to form an air-free ball, when the ball melts, most of the palladium is not diffused and absorbed into the ball and remains near the surface. The palladium remaining near the surface forms a palladium-enriched region on the surface of the ball after solidification. Therefore, the palladium-enriched region has the above-mentioned composition as a trace of palladium remaining near the surface of the air-free ball before solidification. As long as the palladium-enriched region is observed on the surface of the front end of the air-free ball, it can be inferred that a palladium-enriched region in a palladium-enriched state is formed in layers in the vicinity of the entire ball surface or in a partial range including the front end. When bonding with an aluminum electrode, the presence of a palladium-enriched region at the bonding site between the air-free ball and the electrode can improve the bonding reliability of the ball bonding (first bonding).

[0096] When performing free air ball analysis, the palladium-coated copper bonding wire with the structure of forming the palladium-enriched region can prevent shrinkage during the formation of the free air ball. In addition, by using the free air ball having the above-mentioned palladium-enriched region to perform ball bonding with an electrode such as aluminum, the reliability of the ball bonding can be greatly improved.

[0097] The palladium contained in the palladium-enriched region may be derived from the core material, the palladium layer, or both. If such a palladium-enriched region is formed, an excellent effect of improving the bonding reliability of the ball bonding and suppressing the generation of shrinkage cavities in the air-free ball can be obtained. Specifically, according to the palladium-coated copper bonding wire of this embodiment, excellent bonding reliability can be maintained for a long time even in a high temperature and high humidity environment. The palladium concentration in the palladium-enriched region is preferably 7.0 to 25.0 atomic%. If it is within this range, chip damage can be further suppressed and the yield of the semiconductor device can be improved. The palladium-enriched region can be observed by Auger (FE-AES) analysis as described below.

[0098] The palladium-coated copper bonding wire of the present embodiment can form a palladium-rich region by typically containing a chalcogen element in the above-mentioned specific amount in the palladium layer.

[0099] Regarding the measurement conditions when measuring the palladium-enriched area by FE-AES analysis, representatively, for a lead wire with a wire diameter of 10 to 30 μm, preferably 15 to 25 μm, and more preferably 18 to 20 μm, the front end of the airless ball is analyzed from the surface to 100.0 nm in the depth direction by a FE-AES electron spectrometer. Regarding the measurement conditions at this time, for example, as the setting of the FE-AES electron spectrometer, the acceleration voltage of the primary electron beam is 10 kV, the current is 50 nA or less (preferably 50 nA), the acceleration voltage of the argon ion sputtering is 1 kV, and the sputtering rate is 2.5 nm / min (SiO2 conversion). The area of ​​the measurement area calculated by the set value is 15 μm 2 ~20μm 2 , for example, set to a roughly circular or roughly square shape. Specifically, the measurement area can use a roughly circular shape with a diameter of 5μm, or a roughly square shape of 4μm×4μm. It should be noted that the analysis area as the set value is preferably an area with the above area and a smaller outer perimeter, such as a square or a circle. More specifically, a more appropriate analysis can be performed by adjusting in a manner that the maximum distance from the center of gravity of the plane figure formed by at least the outer perimeter of the analysis area to the outer perimeter is less than 3μm. In order to improve the analysis accuracy, Auger analysis is performed at more than 9 points at equal intervals in the depth direction and calculated as the average value. In addition, the measurement area does not take into account the inclination of the sample and can be evaluated as an area where the light beam is assumed to be irradiated perpendicular to the specified plane.

[0100] The palladium-enriched region can be measured as a region containing a depth range of 6.5 to 30.0 atomic % of palladium relative to the total of copper and palladium at each depth of the FE-AES curve at a depth of 5.0 to 100.0 nm from the surface. At this time, depending on the measurement location, it is also possible that the region where the palladium becomes 6.5 to 30.0 atomic % is discontinuous, but in such a case, the range containing the region where all the palladium becomes 6.5 to 30.0 atomic % can be specified as a palladium-enriched region. It should be noted that in the FE-AES curve, since noise caused by attachments, etc. may be included, it is set to be measured from a position with a depth of 5.0 nm from the surface toward the center.

[0101] If the palladium-coated copper bonding wire of the above-mentioned embodiment is used, the palladium concentration of the palladium-enriched area of ​​the air-free ball is generally formed in a manner that the palladium concentration is approximately constant in the depth direction from the surface, or the palladium concentration gradually decreases. Therefore, the palladium-enriched area is preferably in the range of 5nm to 300nm, and more preferably in the range of less than 400nm. That is, it is preferred to observe a palladium-enriched area in which the average concentration of palladium within the range of the preferred thickness from the surface is the above-mentioned specific concentration. This is because: when the palladium-enriched area is thicker, it becomes easier to obtain the effect of improving the bonding reliability. On the other hand, regarding the thickness of the palladium-enriched area, it is believed that: since the palladium concentration relative to the entire lead is the above-mentioned specific concentration, when the lead diameter is 10 to 30μm, it is suppressed to approximately 1.5μm or less, preferably 1.0μm or less. Since the palladium-enriched area is suppressed to the above-mentioned thickness, it becomes less likely to damage the semiconductor chip.

[0102] (Wire bonding structure)

[0103] Next, a wire bonding structure produced using the palladium-coated copper bonding wire according to the present embodiment and a bonding structure analysis will be described. Figure 1 1 is a schematic cross-sectional view showing an example of the wire bonding structure 10 according to the present embodiment. Figure 1 The wire bonding structure 10 shown in FIG. 1 is formed by ball bonding a palladium-coated copper bonding wire to the surface of an electrode 52 containing aluminum on a silicon (Si) substrate 51 . Figure 1 The cross section of the wire bonding structure 10 is shown when it is cut along a plane passing through the center line L in the lead length direction of the palladium-coated copper bonding wire and parallel to the center line L. The wire bonding structure 10 includes a ball bonding portion 20, a bonding surface 21, and a lead portion 22 made of the palladium-coated copper bonding wire. The wire diameter φ of the lead portion 22 is equal to the wire diameter of the palladium-coated copper bonding wire.

[0104] The ball joint 20 is composed of the first ball compression portion 20a on the upper side and the second ball compression portion 20b on the lower side. During ball bonding, the air-free ball formed at the front end of the palladium-coated copper bonding wire is pressed against the electrode 52. The first ball compression portion 20a is a portion where the shape of the air-free ball before ball bonding is relatively maintained, and the second ball compression portion 20b is a portion where the air-free ball is crushed and deformed. In addition, the surface 23 is the surface of the second ball compression portion 20b. X0 in the figure is the maximum width of the second ball compression portion 20b in a direction parallel to the bonding surface 21 (perpendicular to the lead center line L), and Y is the maximum height of the second ball compression portion 20b relative to the bonding surface 21. P1 and P2 are line analysis portions, which are the outer points (points close to each end) of the points that divide the maximum width X0 of the second ball compression portion 20b in a direction parallel to the bonding surface 21 into eight equal parts in a direction perpendicular to the bonding surface 21 (parallel to the lead center line L). It should be noted that, in the case where it is difficult to identify the bonding surface 21, X0 is equivalent to the maximum width of the second ball compression portion 20b in the direction perpendicular to the lead center line L, so it is not a problem. Y can also be calculated from the maximum height based on the contact point between the airless ball and the electrode 52. It should be noted that the size and direction of each part of the ball joint 20 are of course within the error range of measurement.

[0105] The wire bonding structure 10 of the present embodiment has a palladium-rich bonding region near the bonding surface 21 on the electrode 52 , wherein the palladium concentration is 2.0 mass % or more, preferably 5.0 mass % relative to the total of aluminum, copper, and palladium.

[0106] The palladium-enriched bonding region can be evaluated as a predetermined range in which the mass ratio of palladium to the total of palladium, copper and aluminum is 2.0 mass % or more, preferably 5.0 mass % or more, near the bonding surface where the free air ball contacts and bonds with the electrode, that is, in the area where aluminum and palladium coexist. Specifically, a predetermined portion of the cross section of the ball joint 20 is subjected to line analysis by field emission scanning electron microscopy / energy dispersive X-ray spectroscopy (FE-SEM / EDX) from the ball joint 20 side toward the bonding surface 21 in a direction parallel to the lead center line. At this time, at each measuring point within the range where aluminum is more than 0.5 mass % and less than 95.0 mass %, the predetermined range in which the mass ratio of palladium to the total of palladium, copper and aluminum is 2.0 mass % or more, preferably 5.0 mass % or more can be evaluated as a palladium-enriched bonding region. Here, the reason for measuring within the range of aluminum concentration exceeding 0.5 mass % and not more than 95.0 mass % is that the analysis value of a portion without aluminum does not become 0 mass % due to the influence of noise in the analysis, etc., and the analysis value of a portion containing only aluminum does not become 100.0 mass %.

[0107] By having a palladium-enriched bonding area with such a composition, corrosion of the ball bonding part can be suppressed, and fracture and peeling can be prevented to improve bonding reliability. The electrode is formed by, for example, covering the surface of the silicon (Si) base material with electrode materials such as Al, AlSiCu (for example, Al-Cu (0.2 to 0.9 mass%)-Si (0.5 to 1.5 mass%)), AlCu (for example, Al-Cu (0.2 to 0.9 mass%)). In addition, the temperature of the electrode during ball bonding is, for example, 140 to 200°C.

[0108] The palladium concentration in the palladium-enriched bonding region is preferably high, for example, 50.0 mass % or less, usually 30.0 mass % or less, or 20 mass % or less at each measurement point in FE-SEM / EDX line analysis.

[0109] Here, for example, in the above-mentioned wire analysis, for a lead wire with a wire diameter of 10 to 30 μm, when the total of aluminum, palladium and copper in the concentration curve of the FE-SEM / EDX analysis is set to 100 mass %, if the range of the palladium concentration being above 2.0 mass % is above 50 nm, it can be evaluated that there is a palladium-rich bonding area.

[0110] The effect of having a palladium-enriched bonding region in the bonding surface 21 can also be evaluated by the concentration analysis in the above-mentioned line analysis section (P1, P2). Figure 1 In the figure, the outer points (points near the end) of the points obtained by dividing the maximum width X0 of the second ball compression part 20b in a direction roughly parallel to the bonding surface into eight equal parts, and the straight line perpendicular to the bonding surface 21 are set as two line analysis parts P1 and P2, and line analysis is performed from the ball side toward the electrode side by FE-SEM / EDX in the same way as above. At this time, in each line analysis part P1, P2, as long as a palladium-enriched bonding area with a palladium concentration of more than 2% by mass relative to the total of aluminum, copper and palladium is detected, it can be regarded as the presence of a palladium-enriched bonding area near the bonding surface 21. Thus, it can be evaluated that the bonding reliability is maintained for a long time. There is a high possibility that halogen elements and moisture from the sealing resin and the like penetrate from the two ends near the ball bonding surface, that is, the tiny gaps near the bonding part between the ball and the electrode. Therefore, the presence of a palladium-enriched bonding area with high corrosion resistance near the two ends plays a very important role in preventing the penetration of halogens and the like.

[0111] The occupancy rate of the palladium-rich bonding area near the bonding surface 21 between the electrode and the free air ball in the wire bonding structure is preferably 25% or more. This allows excellent high reliability to be maintained. The occupancy rate of the palladium-rich bonding area in the bonding surface is more preferably 50% or more, and further preferably 75% or more.

[0112] The occupancy rate of the palladium-rich bonding area in the bonding surface 21 can be obtained as the width of the palladium-rich bonding area in the direction of the bonding surface 21 in the cut surface relative to the maximum width of the ball joint ( Figure 1 The ratio of X0) shown in is calculated as follows. Figure 1 After obtaining a cut surface as shown in , the cut surface is observed by surface analysis of an electron probe microanalyzer (EPMA) (for example, an accelerating voltage of 15 kV and an irradiation current of 290 nA). In the observed image, the portion where a palladium concentration higher than that of a portion where the palladium concentration is 2.0 mass % or more relative to the total of aluminum, copper and palladium is detected by a palladium (Pd) intensity meter is considered to reflect a palladium-enriched bonding area, and the total width X1 of the portion where the strength becomes stronger is measured. The width X1 is measured as the width in a direction perpendicular to the center line L of the lead. The total of the maximum width X0 of the second ball compression portion 20b in the cut surface and the width of the range where the palladium-enriched bonding area is detected (total width X1) is measured, and the occupancy is calculated as (X1 / X0)×100(%). It should be noted that on the electrode side ( Figure 1 The occupancy rate of the palladium-enriched junction area can be calculated by measuring the width of the curve portion projected onto the maximum width X0 for the curve portion that is not directly connected to the electrode.

[0113] For example, in EPMA measurement (surface analysis), the existence rate of the element of the measurement object is usually measured as the intensity of X-rays emitted from the element when the measurement object is irradiated with electron beams, and the intensity is generally displayed by a color element mapping image reflected in color. That is, in the color element mapping image, points where the element of the measurement object does not exist are displayed as pitch black, and the elements are displayed in the order of high probability of existence, as an example, in the order of "white, red, yellow, green, blue, black" and other levels. In the vicinity of the joint surface 21 on such an EPMA color element mapping image, if the palladium concentration at the point with the smallest palladium intensity (not pitch black on the color element mapping image but the darkest part among the parts where the intensity generated by palladium is observed, such as a blue part close to black in the case of the above-mentioned level) is 2.0 mass% or more, the area displayed with a stronger color can be specified as a palladium-enriched joint area. In addition, the results of the line analysis and the color element mapping image (surface analysis) of EPMA are overlapped, and it is visually determined whether the setting is such that the intensity of the palladium concentration observed in the line analysis to be 2.0 mass% or more and the intensity equal to or greater than the measured point on the color element mapping image can be identified as the intensity difference (color on the image). Thus, the presence and occupancy of the palladium-enriched junction area can be calculated.

[0114] It should be noted that when calculating the occupancy of the palladium-enriched joint region using the color element mapping image of EPMA, the palladium-enriched joint region is sometimes seen in a "sparse" state as the color element mapping image is enlarged. Therefore, it is preferred to calculate the occupancy at a magnification such that at least the second ball compression portion of the ball joint is included in one image. In addition, even if the palladium is in a "sparse" state in the palladium-enriched joint region on the image due to the enlargement of the color element mapping image, or there is a black area in the joint on the EPMA image, as long as the palladium concentration in the line analysis result in the area is detected to be 2.0 mass% or more, the area can be regarded as the palladium-enriched joint region.

[0115] By forming the palladium-enriched bonding region of the embodiment, corrosion of the ball bonding portion can be suppressed, and the ball bonding portion can be prevented from being broken or peeled off due to long-term use, thereby improving bonding reliability. Furthermore, by containing each chalcogen element at the above-mentioned predetermined concentration in the palladium-coated copper bonding wire, the palladium-enriched bonding region can be stably formed regardless of the conditions used within the range of the ball bonding conditions described later. Therefore, for example, if the ball formation conditions are manipulated, the bonding reliability can be significantly improved compared to the conventional method that can achieve the above-mentioned palladium concentration in the ball bonding portion.

[0116] In addition, as a property of the palladium-coated copper bonding wire of the present embodiment, a palladium-enriched bonding region in the wire bonding structure can be confirmed. That is, when a bonding structure is made using the prepared palladium-coated copper wire, and the bonding structure is observed to have the above-mentioned palladium-enriched bonding region, it can be determined that the prepared palladium-coated copper wire contains a chalcogen element in the palladium layer, and satisfies the configuration of the palladium-coated copper bonding wire of the present embodiment that exhibits high reliability for a long time.

[0117] The analysis method for analyzing the bonding structure using a palladium-coated copper wire is described in detail by taking the case of using a pure aluminum electrode as the bonding object. The same is true for the case of using an electrode containing aluminum and an element other than aluminum. A free-air ball is formed using a palladium-coated copper bonding wire, and ball bonding is performed on the aluminum electrode. The ball bonding portion is cut so that the surface parallel to the center line L in the length direction of the lead is exposed. Thus, Figure 1 The cut surface is analyzed from a predetermined position on the lead side in a direction substantially perpendicular to the bonding surface 21 (depth direction). As the line analysis, the above-mentioned FE-SEM / EDX is suitable. It should be noted that the cut surface involved in this analysis is preferably as shown in FIG. Figure 1 As shown in , it is formed so as to include the center line L in the length direction of the lead or to be as close to the center line L as possible.

[0118] The free air ball can be formed under the same conditions as the lead wire analysis with FAB. When the wire diameter of the palladium-coated bonding wire is 10 to 30 μm, preferably 15 to 25 μm, and more preferably 18 to 20 μm, the arc discharge conditions are set in such a way that the discharge current value becomes 30 to 90 mA and the free air ball diameter becomes more than 1.7 times and less than 2.3 times the lead wire diameter. The adapter device can use commercially available products such as the adapter device (IConn ProCu PLUS) made by K&SInc. When using this adapter device, as the settings of the device, it is preferred that the discharge time is 50 to 1000 μs, the EFO-Gap is 25 to 45 mil (about 635 to 1143 μm), and the tail length is 6 to 12 mil (about 152 to 305 μm). When using other adapter devices other than this adapter device, it is only necessary to adjust the setting conditions of the device according to the target ball diameter to obtain the same ball diameter as mentioned above. Furthermore, in order to set the lead tip to a mixed gas atmosphere of nitrogen and hydrogen or a nitrogen atmosphere, the above-mentioned gas is blown at a gas flow rate of, for example, 0.2 to 0.8 L / min, preferably 0.3 to 0.6 L / min, and more preferably 0.5 L / min. The gas used to form the free air ball is preferably a mixed gas of 95.0 volume % nitrogen and 5.0 volume % hydrogen, and the free air ball diameter may be set to the above-mentioned range as a target value.

[0119] In addition, regarding the ball bonding conditions (conditions for the first bonding), for example, for a ball bonding of a lead wire diameter φ of 18 μm and a ball with an airless ball diameter of 32 μm, the height Y of the second ball compression portion 20b can be adjusted by a bonder device in such a way that the height Y of the second ball compression portion 20b becomes approximately 10 μm and the maximum width X0 of the second ball compression portion 20b in a direction approximately parallel to the bonding surface 21 becomes approximately 40 μm. Specifically, as settings of the bonder device, the ball pressing force is 7.5 gf, the ultrasonic applied output power is 70 mA, the ball pressing time is 15 ms, and the pressing temperature is 150°C. In addition, the conditions for the second bonding are, for example, a scraping mode with a pressing force of 70 gf, a pressing time of 20 ms, a pressing temperature of 150°C, a frequency of 200 kHz, an amplitude of 3.0 μm, and a cycle of 2 times. It should be noted that the loop length from the first bonding portion to the second bonding portion can be bonded at 2.0 mm.

[0120] In the analysis test of the ball joint, the cut surface can be made as follows. As a lead frame, for example, a PBGA32PIN frame is used, and a roughly square semiconductor chip is joined to the center of the frame. The aluminum electrode on the semiconductor chip is wire-bonded to the external electrode on the frame using palladium-coated copper bonding wire to make a measurement sample. The palladium-coated copper bonding wire lead is ball-bonded (first bonding) to the aluminum electrode located on the semiconductor chip, and wedge-bonded (second bonding) to the lead frame. Since many electrode columns on the chip are usually arranged in several columns, for example, bonding wires are bonded to the electrodes of one column (8) at equal intervals, and the other 3 columns (3 sides) are also bonded in the same way. Ball bonding is performed with a total of 32 aluminum electrodes. If the wedge bonding with the lead frame is included, the total number of wire bonds is 32.

[0121] Next, the semiconductor chip including 32 sets of joints formed as above is molded by a molding machine using a sealing resin. Once the molding is solidified, the molded part is cut from the frame, and then the vicinity of one row (one side) of the ball joints in the molded part is cut. The cut molding is cut along the cross section of the ball joint ( Figure 1 The cross section as shown in the figure is placed in a cylindrical mold (mold) in a direction that can be ground, and a casting curing agent is added to solidify the embedded resin. After that, the solidified cylindrical resin with the semiconductor chip is roughly ground using a grinder in a manner that the center of the ball joint is exposed as much as possible. The ion milling device is used to make fine adjustments in a manner that once the grinding is completed to the vicinity of the center cross section of the ball joint, the grinding is finally completed and the surface containing the center of the ball (the surface passing through the center line L of the lead part and parallel to the center line L) is just exposed to become the position of the analysis surface. If the lead width of the lead section becomes the length of the lead diameter, the goal is achieved that the cut surface becomes the surface containing the center of the ball. Using the cut surface as the analysis surface, the desired part is subjected to line analysis from the ball side toward the electrode side by field emission scanning electron microscopy / energy dispersive X-ray spectrometry (FE-SEM / EDX). Line analysis conditions are, for example, an acceleration voltage of 6 keV, a measurement area φ of 0.18 μm, and a measurement interval of 0.02 μm.

[0122] Next, the role played by each structure of the palladium-coated copper bonding wire of the present embodiment is described. The reason why the reliability of ball bonding and the suppression of shrinkage cavity generation can be taken into account by the structure of the above-mentioned embodiment is speculated as follows as an example. In ball bonding, an arc discharge is formed at the front end of the lead by an electric discharge welding gun, and the front end of the ball is melted by the heat of the arc current to form an air-free ball. At this time, for the palladium-coated copper lead in which the palladium concentration of the ball joint portion has not been increased so far, the metal and additive elements of the lead that are melted by the arc heat input are diffused and absorbed by the inside of the molten ball in the process of forming an air-free ball. If such a conventional lead is ball-bonded to an electrode containing aluminum, since the vicinity of the bonding surface does not become palladium-enriched, the intermetallic compounds of copper and aluminum, such as Cu9Al4, become easily corroded at the bonding interface between the electrode containing aluminum and the ball joint portion.

[0123] In semiconductor products, the entire wire bond is usually sealed with resin or the like. Halogen elements such as chlorine and bromine from the sealing resin, moisture or sulfur from the atmosphere, etc., penetrate into the ball bonding interface, and corrode the intermetallic compounds of copper and aluminum at the ball bonding interface, which becomes a problem. Moreover, the higher the temperature and humidity of the semiconductor element atmosphere, the more the corrosion tends to be amplified. If the corrosion of the ball bonding interface intensifies, the ball bonding interface will cause peeling and fracture, resulting in an increase in resistance, and poor current conduction will become a problem.

[0124] In contrast, it is believed that in the lead wire of the specific composition and structure of the present embodiment, the diffusion and absorption of palladium into the molten ball is suppressed during the formation of the free air ball, and the unabsorbed palladium is concentrated and distributed near the surface of the ball to cover the surface of the ball. If the free air ball is bonded to an electrode containing aluminum in a state where the surface of the free air ball is covered with the unabsorbed palladium, the bonding interface becomes a state of palladium enrichment with strong corrosion resistance. Therefore, it is speculated that the formation of intermetallic compounds between copper and aluminum is suppressed, and corrosion caused by halogens (especially chlorine), sulfur, water, etc. that invade from the outside is suppressed. As a result, the reliability of ball bonding is improved, and in particular, the reliability under high temperature and high humidity conditions can be significantly improved. From this point of view, the lower limit of the palladium concentration in the lead wire is determined as a range for improving the reliability of ball bonding.

[0125] In particular, when forming the palladium layer of the palladium-coated copper bonding wire, if the palladium coating material contains a chalcogen element at a predetermined concentration, the palladium-rich region on the surface of the free air ball is formed extremely stably. In addition, it is believed that the presence of a predetermined amount of the chalcogen element allows the palladium-rich region to be stably maintained on the surface of the free air ball until bonding with the aluminum electrode, making it easy to form the palladium-rich bonding region of the embodiment. Therefore, according to the wire bonding structure using the palladium-coated copper bonding wire containing the chalcogen element as described above in the lead portion, the bonding reliability under high temperature and high humidity can be significantly improved.

[0126] On the other hand, as described above, even if the surface of the free air ball is set to a palladium-enriched structure, when the use under severe conditions is aimed at, sometimes the bonding reliability is often not improved. The reason is considered that the second bonding object of the wire bonding is often plated with gold or silver on the surface, and the gold or silver derived from the plating adheres to the tail of the wire (the end of the torn wire) when the wire is cut after the second bonding of the wire bonding, causing shrinkage.

[0127] "Shrinkage holes" are wrinkled grooves observed on the surface of the free air ball after solidification. When shrinkage holes exist on the surface of the free air ball after solidification, gaps are generated at the locations corresponding to the above-mentioned grooves on the bonding surface of the ball joint in the electrode on the semiconductor chip. Therefore, it is believed that: depending on the size of the gap, the bonding strength of the bonding surface is weakened over time with the gap as the starting point, or corrosion becomes more likely to occur, thereby reducing the bonding reliability.

[0128] The inventors conducted an in-depth study and found that among the above-mentioned shrinkage holes, there are large shrinkage holes that are problematic and small shrinkage holes that are not problematic. That is, when there are shrinkage holes larger than a specified size on the surface of the air-free ball after solidification, the gap at the interface between the electrode and the ball joint is likely to become larger, and the reduction in the bonding reliability caused by this is significant. In contrast, if the shrinkage hole is smaller than the above-mentioned size, the impact on the bonding reliability is not a problem because the gap is small. As the size of such a shrinkage hole that is not a problem, in the SEM observation photo of the shrinkage hole, the maximum length of the shrinkage hole is less than two-thirds of the diameter of the lead. For example, when the diameter of the lead is 18μm, the shrinkage hole with a maximum length exceeding 12μm can be fully judged as a large shrinkage hole that is problematic. For shrinkage holes below this size, it is estimated that there is almost no impact on the bonding reliability.

[0129] It was also found that the cause of the large shrinkage cavity that is a problem depends on the palladium concentration of the palladium-rich area (actually, an area where palladium and copper are mixed) that covers the surface of the free air ball. That is, if the palladium concentration of the palladium-rich area on the surface of the free air ball exceeds a certain concentration, the inside of the ball is still in a softened state when the palladium-rich area solidifies. Therefore, due to factors such as the difference in composition between the area near the surface of the free air ball where gold is attached and the area where gold is not attached, the difference in solidification rate increases, and the gold-attached area becomes the final solidified part. It is also presumed that when the molten ball becomes solid, the gold-attached part where the shrinkage is concentrated shrinks to the inside of the ball, becoming a large shrinkage cavity that is a problem. This is also the case when silver is attached to the tail.

[0130] On the contrary, it is believed that if the palladium concentration in the palladium-rich region is sufficiently low, the time difference between the solidification of the palladium-rich region and the copper inside the ball becomes small. As a result, even if gold is attached, it does not shrink to the inside of the ball, so large shrinkage holes that become a problem will not be generated. From this point of view, the upper limit of the palladium concentration on the surface of the free air ball is determined. If the ball is bonded to an electrode containing aluminum in a state where a large shrinkage hole is generated in the free air ball, a gap is generated at the interface between the electrode and the ball joint. As a result, the bonding strength of the ball bonding interface is weakened, or corrosion becomes easy to occur, which is a problem.

[0131] The chalcogen in the palladium-coated copper bonding wire contributes to the formation of the palladium distribution area near the surface of the free air ball. It is believed that the chalcogen is highly reactive with copper and therefore concentrates in the contact area between copper and palladium at the initial stage of the metal melting of the lead wire. It is believed that the reaction product of the chalcogen and copper concentrated in the contact area between copper and palladium blocks the melting of palladium into the molten copper. The amount of chalcogen is determined from this point of view.

[0132] In order to obtain the above-mentioned effect, 50.0% or more of the chalcogenide element contained in the entire palladium-coated copper bonding wire is preferably contained between the surface of the palladium-coated copper bonding wire and the portion where the palladium is 50.0 atomic % relative to the total of palladium and copper. It is believed that this makes it easier to form a palladium distribution area near the surface of the free air ball, which can further improve the bonding reliability of the ball bonding.

[0133] (Method for Manufacturing Palladium-Coated Copper Bonding Wire)

[0134] Next, the manufacturing method of the palladium-coated copper bonding wire of the present embodiment is described. The palladium-coated copper bonding wire of the present embodiment is obtained by coating the surface of a copper wire material having copper as the main component as a core material with palladium, performing wire drawing, and performing heat treatment as needed. The palladium coating may be followed by the gold coating, or the palladium or gold coating may be followed by the wire drawing and heat treatment in stages.

[0135] When copper is used as the core material, a copper core material or a copper alloy core material can be obtained by melting copper of a specified purity. In addition, when a copper alloy is used, a copper of a specified purity is melted together with added trace elements. For melting, a heating furnace such as an arc heating furnace, a high-frequency heating furnace, a resistance heating furnace, a continuous casting furnace, etc. is used. In order to prevent the mixing of oxygen or hydrogen from the atmosphere, the atmosphere when the copper is melted in the heating furnace is preferably maintained as a vacuum or an inert gas atmosphere such as argon or nitrogen. The melted core material is cast and solidified from the heating furnace in a manner to become a specified wire diameter, or the molten core material is cast in a mold to make an ingot, and the ingot is repeatedly rolled and drawn to a specified wire diameter to obtain a copper wire.

[0136] As a method for covering the surface of a copper wire with palladium or gold, there are a plating method (wet method) and a vapor deposition method (dry method). The plating method may be any of an electrolytic plating method and an electroless plating method. As for electrolytic plating such as strike plating or thin plating, since the plating speed is fast, if it is used for palladium plating, the adhesion between the palladium layer and the core material is good, so it is preferred. As a method for making the palladium layer contain chalcogen elements by plating, there is the following method: in the above-mentioned electrolytic plating, a plating solution obtained by making the palladium plating solution contain a plating additive containing sulfur, selenium or tellurium is used, and the type or amount of the plating additive is adjusted. Thus, the concentration of chalcogen elements in the lead can also be adjusted.

[0137] As the evaporation method, physical adsorption such as sputtering, ion plating, vacuum evaporation and chemical adsorption such as plasma CVD can be used. According to these methods, it is not necessary to wash the palladium coating or gold coating after formation, and there is no worry about surface contamination during washing. As a method for making the palladium layer contain chalcogen elements by evaporation, there is a method of forming a palladium layer by magnetron sputtering using a palladium target containing chalcogen elements.

[0138] The copper wire coated with palladium and other coatings such as gold as required is then drawn to the final wire diameter and heat treated in this way. The drawing process and heat treatment can also be performed in stages. In addition, in the above, the method of drawing the copper wire coated with palladium and gold to the final wire diameter is described, but the copper wire coated with palladium can also be drawn to a specified wire diameter and then coated with gold, and then drawn to the final wire diameter.

[0139] The processed structure is formed in the copper wire drawing process, and the recrystallized structure is formed by recovery and recrystallization in the heat treatment process. These structures are interrelated and ultimately determine the structure and crystal orientation of the lead wire. The cross-section of the palladium-coated copper bonding wire can be adjusted by optimizing the processing rate and heat treatment conditions after the formation of palladium coating and other coatings formed as needed. <111> and <100> Orientation ratio. Generally, the higher the processing rate, the <111> The more the orientation ratio becomes, <100> In addition, the orientation ratio is controlled by the processing rate rather than the heat treatment conditions, but it can be increased by increasing the heat treatment temperature. <100> The ratio is effective for controlling the orientation ratio by the heat treatment temperature, particularly in a low processing rate range.

[0140] Furthermore, even if the heat treatment temperature is the same, the characteristics of the lead are sometimes affected by the structure or speed of the heat treatment device. In addition, even if the heat treatment conditions are the same in the same device, the characteristics of the lead are sometimes affected by the type or amount of trace elements in the core material. In this regard, in the manufacturing process of the palladium-coated copper bonding wire of the present embodiment, in addition to the above-mentioned processing rate, the crystal orientation ratio of the lead cross section can be controlled by adjusting the elongation during the stress relief heat treatment. The elongation can be mainly controlled by the temperature and time of the stress relief heat treatment. As the crystal orientation ratio of the lead cross section, in order to obtain <100> More than 15% <111> The elongation is preferably adjusted to a range of 5 to 15% as the elongation. Within this elongation range, when the processing rate is low, the elongation is adjusted to a higher level, and when the processing rate is high, the elongation is adjusted to a lower level. <100> Controlled to more than 15%, <111> It is effective to control it to 50% or less.

[0141] The wire drawing process is preferably carried out in stages using multiple diamond wire drawing dies. The cross-sectional shrinkage rate of each diamond wire drawing die has a significant effect on the cross-sectional area of ​​the lead wire. <111> and <100> The influence of the orientation ratio is less than the processing rate, but if the cross-sectional shrinkage is less than 5%, the wire drawing process will increase too much, and if the cross-sectional shrinkage becomes greater than 15%, the tensile force during wire drawing will increase, and wire breakage will occur easily. Considering these, the cross-sectional shrinkage (processing rate) of each diamond wire drawing die is preferably 5.0 to 15.0%.

[0142] In terms of the final wire diameter, a stress relief heat treatment is performed to remove the strain of the metal structure remaining inside the lead. The stress relief heat treatment (tempering heat treatment) takes into account the crystal orientation of the lead cross section and the lead characteristics, and determines the temperature and time in such a way that the elongation is in the range of 5% to 15%. The elongation is set to the value obtained by the tensile test of the bonding wire. The elongation is calculated as the ratio of the elongation length until it breaks when a 10 cm long bonding wire is stretched at a speed of 20 mm / min and a load cell rated at 2N using a tensile test device (such as AUTO COM manufactured by TSE Co., Ltd.). The elongation takes into account the unevenness of the measurement results, and it is preferably calculated as the average value of 5 wires.

[0143] In addition, heat treatment corresponding to the purpose can also be performed at any stage of lead manufacturing. As such heat treatment, there is a diffusion heat treatment in which adjacent metals are diffused to each other after palladium coating or gold coating to improve the bonding strength. By performing diffusion heat treatment, the bonding strength between dissimilar metals can be improved. Regarding the diffusion heat treatment conditions, the temperature and time are also determined in consideration of the required lead characteristics.

[0144] Regarding the method of heat treatment, mobile heat treatment in which the lead wire is passed through the atmosphere of a heating container heated to a predetermined temperature is preferably used because it is easy to adjust the heat treatment conditions. In the case of mobile heat treatment, the heat treatment time can be calculated by the passing speed of the lead wire and the passing distance of the lead wire in the heating container. As the heating container, a tubular electric furnace or the like is used.

[0145] According to the palladium-coated copper bonding wire of the present embodiment described above, shrinkage cavities during ball formation can be suppressed, and ball bonding reliability is excellent even under high temperature and high humidity conditions, and further, the roundness of the first bonding shape can be improved even in narrow pitch bonding. Therefore, a wire bonding structure with extremely high long-term reliability can be formed, and thus it is suitable for QFP (Quad Flat Packaging), BGA (Ball grid array), and QFN (Quad For Non-Lead Packaging). In addition, since a wire bonding structure with high reliability can be formed, it is suitable for use in high temperature and high humidity environments such as vehicle-mounted equipment. Furthermore, since the roundness of the first bonding is improved, it is also suitable for narrow pitch bonding structures such as small semiconductor equipment.

[0146] (Semiconductor device and method of manufacturing the same)

[0147] Next, a semiconductor device using the palladium-coated copper bonding wire of the above-described embodiment will be described. Figure 7 As shown in , the semiconductor device 1 of this embodiment includes a semiconductor chip 2, an aluminum electrode 3 containing aluminum provided on the semiconductor chip 2, an external electrode 4 covered with gold provided outside the semiconductor chip 2, and a bonding wire 5 connecting the aluminum electrode 3 to the surface of the external electrode 4. It should be noted that Figure 7 In the description, the case where the external electrode is covered with gold is taken as an example, but the same is true if the external electrode is covered with silver instead of gold or together with gold.

[0148] In the semiconductor device 1, the bonding wire 5 is made of the palladium-coated copper bonding wire of the above embodiment. In addition, the bonding surface between the aluminum electrode 3 and the bonding wire 5 has a palladium-rich bonding region in which the palladium concentration is 2.0 mass % or more relative to the total of the constituent elements of the surface of the aluminum electrode 3 and copper and palladium.

[0149] The semiconductor chip 2 has an integrated circuit (IC) including a silicon (Si) semiconductor or a compound semiconductor. The aluminum electrode is formed by, for example, covering the surface of a silicon (Si) matrix with an electrode material such as Al, AlSiCu, or AlCu. The external electrode 4 is an electrode for supplying power to the semiconductor chip 2 from the outside. The power from the external electrode 4 is supplied to the semiconductor chip 2 via a bonding wire 5.

[0150] In the manufacture of the semiconductor device 1 of the present embodiment, the connection between the aluminum electrode 3 and the external electrode 4 using the bonding wire 5 is performed, for example, as follows. Using a bonding device or a capillary fixture through which the bonding wire is passed for connection, heat is input to the front end of the lead held by the capillary by, for example, arc discharge, so that the front end of the lead is heated and melted. As a result, a free air ball is formed at the front end of the lead. Thereafter, for example, while the semiconductor chip 2 is heated in the range of 140 to 200° C., the free air ball is crimped and bonded to the aluminum electrode 3 to form a ball bond (first bond). Thereafter, the end of the bonding wire 5 on the opposite side of the first bond separated by a predetermined interval is directly wedge-bonded to the external electrode 4 by ultrasonic crimping (second bond).

[0151] In the manufacturing method of the semiconductor device of the present embodiment, the conditions for forming the free air ball are the same as those described above. Specifically, for example, when a bonder device is used, when the wire diameter of the bonding wire 5 is 10 to 30 μm, preferably 15 to 25 μm, and more preferably 18 to 20 μm, the arc discharge current value is 30 to 90 mA. In ordinary bonding, the arc discharge conditions are set in such a way that the free air ball diameter is more than 1.7 times and less than 2.3 times the lead wire diameter. In narrow pitch bonding, although it also varies depending on the width of the electrode interval, for example, when the wire diameter of the bonding wire 5 is 18 μm, the arc discharge conditions are set in such a way that the free air ball diameter is 1.5 to 1.7 times the lead wire diameter. The bonder device can use commercially available products such as a bonder device (fully automatic Cu wire bonder; IConn ProCu PLUS) manufactured by K&S Inc. When using this adapter device, as the settings of the device, the discharge time is preferably 50 to 1000 μs, the EFO-Gap is 25 to 45 mil (about 635 to 1143 μm), and the tail length is 6 to 12 mil (about 152 to 305 μm). In the case of other adapter devices other than this adapter device, as long as the conditions are the same as those above, for example, the conditions that the free air ball diameter becomes the same size as above will suffice. In addition, in order to set the lead tip to a mixed gas atmosphere of nitrogen and hydrogen or a nitrogen atmosphere, the above-mentioned gas is blown at a gas flow rate of 0.2 to 0.8 L / min, preferably 0.3 to 0.6 L / min. The gas when the free air ball is formed is preferably a mixed gas of 95.0 volume % nitrogen and 5.0 volume % hydrogen, and the free air ball diameter can be in the above range based on the target value.

[0152] In addition, the conditions of ball bonding and wedge bonding can be appropriately adjusted according to the structure and application of the semiconductor device. For example, for ball bonding of a lead wire diameter φ of 18 μm and a ball diameter of 32 μm, the settings of the bonder device are as follows: the ball pressing force is 7.5 gf, the ultrasonic application output power is 70 mA, the ball pressing time is 15 ms, and the pressing temperature is 150° C. Thus, the ball bonding can be formed with the height Y of the second ball compression part 20 b being approximately 10 μm and the maximum width X0 of the second ball compression part 20 b in a direction approximately parallel to the bonding surface 21 being approximately 40 μm. Wedge bonding can be performed by using a scraping mode with a pressing force of 70 gf, a pressing time of 20 ms, a pressing temperature of 150° C., a frequency of 200 kHz, an amplitude of 3.0 μm, and a cycle of 2 times, with the loop length set to 2 mm.

[0153] The method for manufacturing a semiconductor device of an embodiment manufactures a semiconductor device having a semiconductor chip, an aluminum electrode containing aluminum disposed on the semiconductor chip, an external electrode disposed outside the semiconductor chip and having a gold coating or a silver coating, and a bonding wire connecting the aluminum electrode to the surface of the external electrode. The bonding wire is a palladium-coated copper bonding wire having a core material having copper as a main component and a palladium layer on the core material, and containing a chalcogen. The palladium concentration is 1.0 mass % to 4.0 mass % and the total chalcogen concentration is 5.0 mass % to 50 mass ppm relative to the total of copper, palladium and chalcogen in the palladium-coated copper bonding wire. The manufacturing method comprises the following steps: a step of forming a free air ball having a palladium-enriched region with an average palladium concentration of 6.5 atomic % to 30.0 atomic % relative to the total palladium of copper and palladium within a range of 5.0 nm to 100.0 nm from the surface of the front end portion of the ball at the front end of the palladium-coated copper bonding wire; a step of bonding the palladium-coated copper bonding wire to the aluminum electrode through the free air ball; and a step of bonding a portion separated from the free air ball by approximately the length of the palladium-coated copper bonding wire to the surface of the external electrode.

[0154] The semiconductor device of the embodiment is suitable for, for example, a QFP (Quad Flat Packaging), a BGA (Ball grid array), or a QFN (Quad For Non-Lead Packaging) used in a printed wiring board or the like.

[0155] According to the semiconductor device of the present embodiment described above, in wire bonding, the shrinkage of the ball during ball bonding can be suppressed, the reliability of ball bonding is excellent even under high temperature and high humidity, and the roundness of the first bonding shape can be improved. Therefore, since a bonding structure with extremely high long-term reliability can be formed, it is suitable for use in high temperature and high humidity environments such as vehicle-mounted equipment. In addition, according to the manufacturing method of the semiconductor device of the present embodiment, a bonding structure with high long-term reliability can be formed not only in ordinary bonding but also in narrow pitch bonding, so a semiconductor device suitable for use in high temperature and high humidity environments such as vehicle-mounted equipment can be obtained. In addition, a small semiconductor device with extremely high reliability and narrow pitch bonding can be provided.

[0156] Example

[0157] Next, examples will be described. The present invention is not limited to the following examples. Examples 1 to 17 and Examples 31 to 39 are examples, and Examples 18 to 30 and Examples 40 to 43 are comparative examples.

[0158] The core material uses copper (Cu) with a purity of 99.99% by mass or more, which is continuously cast, rolled while being pre-heat treated, and then drawn once to obtain a copper wire with a wire diameter of 18 to 500 μm. For the lead containing trace elements (one or more of P, Pt, Pd, Rh, Ni, and In) in the copper core material, a copper alloy wire is obtained in the same manner as above using a copper alloy to which each trace element is added in a manner to obtain a specified concentration recorded in each table. Each trace element uses a raw material with a purity of 99.99% by mass or more. Below, the case of manufacturing a palladium-coated copper bonding wire using a copper wire is described, but the same is true for the case of using a copper alloy wire.

[0159] The palladium coating layer was formed as follows. Additives containing sulfur, selenium, and tellurium were added to a commercially available palladium electroplating bath, and the concentrations of sulfur, selenium, and tellurium in the plating bath were controlled so that the concentration relative to the entire lead (the total of copper, palladium, and chalcogen elements) became the concentrations described in the following table. Plating baths were prepared. The copper wire was immersed in the plating bath and a current density of 0.75 A / dm was passed through the copper wire. 2 A current is passed to form a palladium coating containing sulfur, selenium or tellurium. When forming a palladium coating containing two or more of sulfur, selenium and tellurium, two or more plating baths to which the above additives are added are used.

[0160] After that, the wire was drawn twice continuously in a wet process through a diamond wire drawing die without baking treatment. As for the final wire diameter, a tempering heat treatment was performed by adjusting the heat treatment temperature and the heat treatment time so that the elongation was in the range of 6% to 14% in the embodiment, and a palladium-coated copper bonding wire with a wire diameter of 18μm or 25μm was obtained.

[0161] The processing rate of each example calculated from the lead cross-sectional area before and after drawing from the covered lead to the final wire diameter was in the range of 52% to 99.9% in the Examples, and the wire speed during the wire drawing process was 100 to 1000 m / min.

[0162] The palladium-coated copper bonding wire with a gold layer is manufactured as follows. In the manufacturing process of the palladium-coated copper bonding wire, after being coated with palladium, gold plating is further performed using a commercially available gold plating bath. It should be noted that the concentration of each element in the table is calculated without including the gold concentration of the gold layer in the entire lead.

[0163] The palladium concentration in the palladium-coated copper bonding wire was measured as follows. The manufactured lead was dissolved in about 1000 m of aqua regia, and the concentration of palladium (Pd) in the solution was determined by high-frequency inductively coupled plasma emission spectrometry (ICPS-8100 of Shimadzu Corporation). The obtained value is shown in the "Pd (Pd layer source)" column of the following table. It should be noted that in the following table, the abbreviation "mass" refers to mass.

[0164] The concentration of chalcogens in the palladium-coated copper bonding wire was measured as follows. The manufactured wire was dissolved in about 100 m of aqua regia, and the concentration of sulfur (S), selenium (Se), or tellurium (Te) in the solution was determined using an inductively coupled plasma mass spectrometer (Agilent 8800 manufactured by Agilent Technologies, Inc.). The values ​​obtained are shown in the "Chalcogens" column of the following table.

[0165] The compositions of the palladium-coated copper bonding wires of the examples and comparative examples obtained above are shown in Tables 1, 2, and 5. The thickness of the gold layer is a value obtained by calculating the mass of gold per unit length from the gold concentration and the specific gravity of gold, assuming that the lead cross section is a true circle for the lead per unit length, and that gold is uniformly present on the outermost surface. Next, the following characteristics of the palladium-coated copper bonding wires obtained above were evaluated.

[0166] (Observation of lead surface cracking)

[0167] A torsion test was performed on a copper wire after palladium plating (a wire having a gold layer after being covered with gold). The appearance of the wire surface after the torsion test was observed by an optical stereo microscope (manufactured by Olympus Corporation, product name: SZX16), and the evaluation was performed by whether the cracks of the palladium reached the copper of the core material. The wire in which the cracks did not reach the copper was evaluated as having no lead surface cracks (○), and the wire in which the cracks reached the copper was evaluated as having lead surface cracks (×). The torsion test was performed using an apparatus manufactured by Maekawa Testing Instruments (device name: TO-202). The two ends of the lead sampled at about 20 cm were fixed, and the lead was rotated 180 degrees clockwise and 180 degrees counterclockwise. After 7 sets of this, the appearance was observed. The results are shown in Tables 3 and 4. It should be noted that for the lead in which the cracks reached the copper, since the subsequent wire drawing process, shrinkage cavity, HAST evaluation, etc. were not implemented, it is indicated as not implemented (-) in the table.

[0168] (Measurement of crystal orientation of lead cross section)

[0169] The crystal orientation of the lead cross section is measured as follows. Prepare a plurality of lead samples obtained by cutting the produced palladium-coated copper bonding wire into a length of several centimeters. Considering that the lead sample is not stretched or relaxed, it is attached straight and flat to the metal (Ag-plated frame) plate. Thereafter, the lead sample is placed in a cylindrical mold (mold) together with the metal plate in such a way that the metal plate becomes the bottom surface of the cylinder, and the resin is poured into the mold, and then a curing agent is added to cure the resin. Next, the cured cylindrical resin containing the lead sample is roughly ground using a grinder in such a way that a vertical cross section in the length direction of the lead is exposed. Thereafter, the cut surface is finished by final grinding, and then, the residual strain of the ground surface is removed by ion milling to obtain a smooth surface. It should be noted that the ion milling device is finely adjusted in such a way that the cut surface of the lead becomes perpendicular to the length direction of the lead.

[0170] The cross section of the lead sample (i.e., the polished surface of the sample) is attached to the sample stage of a field emission scanning electron microscope (FE-SEM) in such a way that it becomes parallel to the sample stage, and the crystal orientation of the cross section is measured by setting the observation magnification of 2500 times, the acceleration voltage of 20keV, the measurement area of ​​about 21×21μm, the measurement interval (Step Size) of 0.06μm, and the standard phase (Phase) of Copper by FE-SEM. The crystal orientation obtained by such operation is analyzed using a dedicated software for crystal orientation analysis (OIM analysis manufactured by TSL). In the crystal orientation analysis using the pattern data obtained by the EBSP method, it is necessary to pre-set the crystal system (standard phase) of the sample from which the pattern data is obtained in the dedicated software, and select the standard pattern file (material file) of the analysis object element attached to the dedicated software to perform the analysis. That is, in the case of alloys other than the pure gold family, a material file with the same composition as the sample is usually required, but since the copper core material formed of the copper alloy used in this embodiment has a very small amount of trace elements, it can be confirmed that the crystal system of the copper core material itself made of the copper alloy is roughly the same as that of pure copper with the same processing conditions. In addition, since the palladium concentration of the entire lead is also low, it is also confirmed that the cross-sectional area of ​​the palladium layer accounts for a low proportion of the cross-sectional area of ​​the lead, and the structure of the palladium layer in the present invention has little effect on the crystal orientation ratio of the cross-sectional area of ​​the lead. Therefore, in the crystal orientation analysis, copper (Copper) is selected as the standard phase (Phase) of the material pattern of the dedicated software. In addition, in the EBSP method, the magnification, acceleration voltage, measurement area, and measurement interval can be set according to the size of the lead sample and the purpose of the analysis, but in this embodiment, the conditions that can be effectively measured are selected in consideration of the measurement time and measurement accuracy, but it is also confirmed that: before and after this condition, there is no effect on the measurement result of the crystal orientation of the cross-sectional area of ​​the lead.

[0171] The crystal orientation of the sample to be measured is analyzed by setting the crystal grain identification conditions of the dedicated software. The crystal grain identification conditions of the dedicated software can usually be set according to the purpose of analysis, but since the analysis results of the crystal orientation are basically not affected, in this embodiment, it is set to identify 1 crystal grain when the orientation difference is less than 15° and more than 5 pixels are connected, and the crystal orientation of the sample to be measured is analyzed. <111> , <100> The ratio of grains with a predetermined orientation is determined by taking the lead length direction as the reference, and the angle difference of each crystal orientation is within 15°. <111> and <100> The ratio of orientation.

[0172] In addition, in the analysis of EBSP measurement data, there may be areas where the crystal orientation cannot be measured due to the roughness of the measurement surface, residual strain caused by grinding, etc., contamination, the presence of oxide film, etc. Therefore, a reliability is set, and the area of ​​only the crystal orientation that can be identified in the measurement area is set as a whole based on the reliability, and the ratio of each orientation (hereinafter referred to as the orientation ratio) is automatically calculated by dedicated software. That is, the location where the crystal orientation cannot be measured, or even if it can be measured but the reliability of the orientation analysis is low, is excluded to obtain the orientation ratio. Here, the so-called reliability is sometimes prepared in the analysis software as a parameter, for example, the Confidential Index (CI value), Image Quality (IQ value) and other parameters can be used to select the judgment standard according to the sample state, the purpose of analysis, etc. For example, the CI value is set to 0.1 or more, and the location with a CI value less than 0.1 is excluded. Furthermore, the purification function prepared in the analysis software is used to replace the orientation data of the point that cannot be measured well with the data of the pixels that have been measured normally around it, and the incomplete part of the measurement is supplemented. This method is effective in removing the points that cannot be measured well when they exist sporadically. However, excessive purification may cause artifacts, so for example, for identification of crystal grains, the orientation difference is set to be 15° or less and 5 or more pixels are connected, and the Grain Dilation method is performed once, and the Grain CI Standardization method is further performed once.

[0173] (Free Air Ball Analysis)

[0174] For the palladium-coated copper bonding wire with a wire diameter of 18 μm obtained in Example 1, an arc discharge current value (discharge ball formation (EFO) current value) was set to 65 mA using an ultrasonic device (fully automatic Cu wire bonder; IConn ProCu PLUS) manufactured by K&S Inc., and the discharge time was adjusted within the range of 50 to 1000 μs to form a free air ball with a ball diameter (FAB diameter) of about 32 μm (about 1.8 times the lead wire diameter). The free air ball forming atmosphere was a mixed gas of 95.0 volume % nitrogen and 5.0 volume % hydrogen, and the gas was blown to the lead wire tip at a gas flow rate of 5.0 L / min. The approximate center of the front end side (opposite to the lead wire neck) of the formed free air ball was analyzed in the depth direction by a scanning Auger electron spectrometer (JAMP-9500F (device name) manufactured by JEOL Ltd.). The setting conditions of the Auger electron spectrometer are: the acceleration voltage of the primary electron beam is 10 kV, the current is 50 nA, the beam diameter is 5 μm, the acceleration voltage of the argon ion sputtering is 1 kV, and the sputtering rate is 2.5 nm / min (SiO2 conversion). The average concentration of palladium relative to the total of copper and palladium is obtained when 9 or more points are analyzed at equal intervals from the surface of the front end of the airless ball to 5.0 to 100.0 nm in the depth direction. Specifically, the analysis site is 31 sites every 1.0 nm from the surface to approximately 0 to 30.0 nm, 5 sites every 6 nm from 31.0 to 60.0 nm, and 35 sites every 12.0 nm from 61.0 to 480.0 nm.

[0175] In other examples, the palladium-coated copper bonding wire obtained above is bonded using the same fully automatic Cu wire bonder as in Example 1, and as described in the table, the discharge ball formation (EFO) current is adjusted to the specified values ​​in the range of 30 to 90 mA and the discharge time is adjusted to the specified values ​​in the range of 50 to 1000 μs in the same manner as in Example 1 so that the ball diameter becomes a specified size in the range of 1.8 to 2.3 times the wire diameter, and an air-free ball is formed under the same conditions as in Example 1. For Examples 10 and 31, a copper core material containing 1.3 mass ppm of palladium relative to the core material as a whole is used. For the air-free balls obtained in each example, the average concentration of palladium from the surface of the front end of the ball to 5.0 to 100.0 nm in the depth direction is determined in the same manner as in Example 1. The results are shown in the "Surface Pd Concentration" column of the lead analysis with FAB in the table together with the composition of the lead and the air-free ball formation conditions. In addition, Figure 4 : The Auger analysis curve in the depth direction from the tip of the free air ball of Example 14 is shown. It should be noted that in Examples 2 to 17 and Examples 31 to 39, the average concentration of palladium from the tip surface of the ball to 5.0 to 100.0 nm in the depth direction was obtained, but the average concentration of palladium was in the range of 5.0 to 400.0 nm, which was also a concentration of the same degree as the value in the following table.

[0176] (Shrinkage Evaluation)

[0177] In addition, 30 airless balls made under the same conditions as above were observed by SEM to see if there were large shrinkage cavities on the surface of the balls. In the SEM observation photos, shrinkage cavities with a maximum length of more than 12 μm were evaluated as problematic shrinkage cavities, and shrinkage cavities with a length of less than 12 μm were evaluated as non-problematic shrinkage cavities. Figure 2 The free air ball with small shrinkage cavities that are not a problem is shown in FIG. Figure 3 The non-air sphere in FIG. 1 shows a large shrinkage cavity that is a problem. The shrinkage cavity is surrounded by a dotted line in the photo. Figure 3 A free air ball without shrinkage cavities or a free air ball with small shrinkage cavities that are not a problem was evaluated as having no shrinkage cavities (○), and a free air ball with even one shrinkage cavity that could be a problem was evaluated as having shrinkage cavities (×).

[0178] (True roundness)

[0179] The roundness of the first joint is divided into the case of normal joint and the case of narrow pitch joint as follows. In the case of normal joint, in Example 1 where the diameter of the air-free ball is 32 μm, an air-free ball is formed in the same manner as described above. Moreover, the conditions of ball bonding are adjusted using a bonder device (ball pressing force is 7.5 gf, ultrasonic applied output power is 70 mA, ball pressing time is 15 ms, and pressing temperature is 150°C) in such a manner that the height Y of the second ball compression portion 20b becomes 10 μm and the maximum width X0 of the second ball compression portion 20b in a direction parallel to the bonding surface 21 becomes 40 μm, and a ball bond is formed on the aluminum electrode of the chip. In other embodiments, the ball bonding conditions are adjusted in such a manner that the maximum width X0 of the above-mentioned bonding surface becomes approximately 1.2 to 1.3 times the ball diameter.

[0180] Regarding the evaluation of the roundness of the ball part in the ordinary joint, for the first joint of 100 balls, the joined balls are observed from the top, the maximum width of the crimped ball and the width perpendicular to it are measured, and the ratio of the maximum width to the width perpendicular to it (maximum width / orthogonal width) is calculated. If the average value of the ratio of the above 100 balls is 1.15 or more, it is judged as poor (marked as "D"); if it is 1.1-1.15, it is judged as an improvement in expected mass production (marked as "C"). In the case where the ratio is less than 1.1, it is divided into two types. The case where there is a ball with a ratio (maximum width / orthogonal width) value of 1.1 or more is judged as good (marked as "B"), and the case where there is no ball with a value of more than 1.1 is judged as very good (marked as "A").

[0181] The roundness of narrow pitch bonding is performed as follows. Using the same fully automatic Cu wire bonder as the above-mentioned free air ball analysis, as recorded in the table, the discharge ball formation (EFO) current is adjusted to a specified value in the range of 65mA and the discharge time is adjusted to a specified value in the range of 50 to 1000μs in such a way that the ball diameter becomes a specified size in the range of 1.5 to 1.7 times the wire diameter, and a free air ball is formed and crimped onto the electrode. In the first bonding, the bonding conditions of the above-mentioned ordinary bonding are adjusted in such a way that the maximum width X0 of the bonding ball becomes approximately 1.2 to 1.3 times the ball diameter. The maximum width X0 of the bonding ball is approximately 35μm in Example 1.

[0182] Regarding the evaluation of the roundness of the ball joint of the small-diameter ball used in the narrow pitch joint, for the first joint of 100 balls, the joined balls are observed from the top, the maximum width of the crimped ball and the width perpendicular to it are measured, and the ratio of the maximum width to the width perpendicular to it (maximum width / orthogonal width) is calculated. If the average value of the ratio of the above 100 balls is 1.1 or more, it is judged as poor (marked as "D"), and if it is 1.05 to 1.1, it is judged to be improved (marked as "C"). In the case where the ratio is less than 1.05, it is divided into two types. The case where there is a ball with a ratio (maximum width / orthogonal width) value of 1.05 or more is judged as good (marked as "B"), and the case where there is no ball with a value of more than 1.05 is judged as very good (marked as "A").

[0183] (Production of test pieces for HAST and HTS)

[0184] For the palladium-coated copper bonding wire obtained in each example, test pieces were prepared as follows, and bonding reliability evaluations of normal bonding and narrow pitch (small diameter ball) bonding were performed. Using the same fully automatic Cu wire bonder device as described above, wire bonding was performed on a 2 μm thick Al-1.0 mass % Si-0.5 mass % Cu alloy electrode on a 400 μm thick Si chip on a BGA (ball grid array) substrate under the same conditions as normal bonding, narrow pitch bonding of airless balls, ball bonding, and second bonding in the roundness evaluation.

[0185] Regarding the conditions for the first bonding, for example, for Example 1 in which the lead wire diameter φ is 18 μm, a free air ball with a ball diameter of 32 μm is formed. In addition, in such a manner that the height Y of the second ball compression portion 20b becomes 10 μm and the maximum width X0 of the second ball compression portion 20b in the direction parallel to the bonding surface 21 becomes 40 μm, the ball bonding is performed with the electrode by adjusting the ball pressing force of 7.5 gf, the ultrasonic applied output power of 70 mA, the ball pressing time of 15 ms, and the pressing temperature of 150°C using the above-mentioned fully automatic Cu wire bonder device. In addition, the second bonding is performed by wedge bonding using the scraping mode under the conditions of a pressing force of 70 gf, a pressing time of 20 ms, a pressing temperature of 150°C, a frequency of 200 kHz, an amplitude of 3.0 μm, and 2 cycles, and 1000 wires are bonded with a loop length of 2 mm.

[0186] At this time, only the adjacent joints of the Al-1.0 mass% Si-0.5 mass% Cu alloy electrodes on the chip are electrically connected, and one circuit is electrically formed by two adjacent leads, forming a total of 500 circuits. Afterwards, the Si chip on the BGA substrate was resin-sealed using a commercially available transfer molding machine (Dai-ichi Seiko Co., Ltd., GPGP-PRO-LAB80) to obtain a test piece. It should be noted that the sealing resin used a commercially available non-halogen-free resin. In addition, for test pieces other than Example 1, ball bonding was performed in a manner such that the height Y of the second ball compression portion 20b became 7 to 13 μm and the maximum width X0 of the second ball compression portion 20b in a direction parallel to the bonding surface 21 became 1.2 times that of the airless ball formed.

[0187] Regarding the conditions for narrow pitch (small diameter ball) bonding, for example, in Example 1 where the lead wire diameter φ is 18 μm, an airless ball with a ball diameter of 30 μm is formed in the first bond. Then, in such a manner that the height Y of the second ball compression part 20b becomes 9 μm and the maximum width X0 in the direction parallel to the bonding surface 21 of the second ball compression part 20b becomes 35 μm, the ball pressure bonding force is adjusted to 7 gf, the ultrasonic application output power is adjusted to 65 mA, the ball pressure bonding time is adjusted to 15 ms, and the bonding temperature is adjusted to 150 °C using the above-mentioned fully automatic Cu wire bonder device, and ball bonding is performed with the electrode. In addition, the second bond is performed by wedge bonding under the conditions of a pressure bonding force of 70 gf, a pressure bonding time of 20 ms, a pressure bonding temperature of 150 °C, a frequency of 200 kHz, an amplitude of 3.0 μm, and 2 cycles in the scratch mode, and 1000 leads are bonded with a loop length of 2 mm. For test pieces other than Example 1, the first (ball) bond is performed in such a manner that the height Y of the second ball compression part 20b becomes 6 to 12 μm and the maximum width X0 in the direction parallel to the bonding surface 21 of the second ball compression part 20b becomes 1.2 times the formed airless ball. It should be noted that the formation of the airless ball is adjusted under the condition that the airless ball diameter becomes approximately 1.5 to 1.7 times the lead wire diameter in the same manner as the above-mentioned airless ball analysis for the above-mentioned fully automatic Cu wire bonder device.

[0188] <HAST (Highly Accelerated Temperature and Humidity Stress Test) (High Temperature and High Humidity Environmental Exposure Test)>

[0189] For this test piece, using a HAST device (Hirayama Seisakusho Co., Ltd., PCR8D), it is maintained at 130 °C × 85.0% RH (relative humidity) for 400 hours and 600 hours. The resistance values of the above-mentioned 500 circuits are measured before and after the maintenance at each time. If there is even one circuit whose resistance value after the maintenance exceeds 1.1 times the resistance value before the maintenance, it is evaluated as defective (×), and if the resistance values of all 500 circuits are lower than 1.1 times, it is evaluated as excellent (◎). After maintaining for 400 hours, the resistance of all samples is lower than 1.1 times.

[0190] <HTS (High Temperature Storage Test) (High Temperature Storage Test)>

[0191] In addition, the test piece was kept at 220°C for 2000 hours using an HTS device (DRS420DA manufactured by Advantech Co., Ltd.). The resistance values ​​of 500 circuits were measured in the same manner as above before and after the holding. If even one circuit had a resistance value after the holding that exceeded 1.1 times the resistance value before the holding, it was evaluated as poor (×), and if all 500 circuits had a resistance value less than 1.1 times, it was evaluated as excellent (◎). The evaluation results of the HAST test and the HTS test are shown in Tables 3, 4, and 6. The "number of poor results" in Table 4 is the number of circuits whose resistance value after the holding exceeded 1.1 times the resistance value before the holding.

[0192] <Analysis of Wire Bonding Structure>

[0193] The observation of the palladium-enriched joint area is carried out as follows. Using the lead made in Example 31, an airless ball is formed in the same manner as the conditions for making the test pieces for HAST and HTS mentioned above. Moreover, the conditions for ball bonding are adjusted using a bonder device in such a manner that the height Y of the second ball compression portion 20b becomes 10 μm and the maximum width X0 of the second ball compression portion 20b in a direction parallel to the bonding surface 21 becomes 40 μm, and a ball bond is formed on the aluminum electrode of the chip. The obtained ball joint is molded by the above method and cut using an ion milling device (IM4000 manufactured by Hitachi High-Technologies) in such a manner that the surface parallel to the center line in the length direction of the lead is exposed. The cut surface is subjected to line analysis by field emission scanning electron microscopy / energy dispersive X-ray spectroscopy (FE-SEM / EDX) from a specified position on the lead side in a direction perpendicular to the bonding surface. Regarding the analysis conditions, as the setting of FE-SEM / EDX, the acceleration voltage is 6 keV, the measurement area φ is 0.18 μm, and the measurement interval is 0.02 μm. The line analysis site and Figure 1 That is, the line analysis was performed in a manner such that the maximum width of the second ball compression portion in the direction parallel to the bonding surface was located at a point that was one eighth of the distance from both ends. The obtained FE-SEM / EDX curve is shown in Figure 5 and Figure 6 In. By Figure 5 , 6 It was found that near the joint surface where aluminum was more than 0.5 mass% and less than 95.0 mass%, there was a palladium-enriched joint region where the ratio of palladium to the total of aluminum, copper and palladium was more than 2.0 mass%. In addition, the width (depth) of the palladium-enriched joint region was about 220 nm as an average of two points.

[0194] Similarly to the above, for Examples 32 to 39, line analysis was also performed on the same two line analysis parts mentioned above. The case where the palladium-enriched bonding area with a palladium concentration of 2.0 mass % or more relative to the total of aluminum, copper and palladium was observed in two of the two locations was set as "yes", and the case where it was not observed in two of the two locations was set as "no". It should be noted that there is no example where it was observed in only one place. Their results are shown in Table 6. There is a high possibility that halogen elements and moisture from sealing resins, etc. gradually penetrate from the tiny gaps at both ends near the ball joint surface. Therefore, the presence of a palladium-enriched bonding area with high corrosion resistance near both ends of the analyzed part can play a very important role in preventing the infiltration of halogens, etc. It should be noted that the depth (width in the depth direction) of the line analysis part where the palladium-enriched bonding area was observed shown in Table 6 is all above 50nm.

[0195] <Occupancy of Palladium-enriched Junction Area>

[0196] The occupancy rate of the palladium-enriched bonding area is calculated by the above-mentioned method. That is, the cut surface is observed by surface analysis of an electron probe microanalyzer (EPMA) (accelerating voltage of 15 kV, current value of 290 nA), and the intensity difference of the palladium element is used to identify the palladium-enriched bonding area, which is set to the total width X1 of the range in which it is detected. Using the maximum width X0 of the second ball compression portion 20b in the bonding surface and the above-mentioned total width X1, the occupancy rate ((X1 / X0)×100(%)) is calculated. In addition, in the surface analysis of EPMA, the point with the lowest palladium intensity near the bonding surface 21 (the part with the lightest color in the image) is line analyzed by FE-SEM / EDX, and the results confirm that the palladium concentration is greater than 2.0 mass% relative to the total of aluminum, copper and palladium. That is, it is known that all the parts calculated as occupancy rates are palladium-enriched bonding areas.

[0197] It should be noted that, in Examples 18 to 20, the plated copper wire had a plated wire diameter of 500 μm, and the thickness of the palladium coating layer was plated with Pd in ​​such a way that it became 1.8 μm in Example 18, 2.1 μm in Example 19, and 1.9 μm in Example 20. Since the cracks on the surface of the lead reached the copper of the core material in the torsion test after plating, resulting in cracks on the surface of the lead, no subsequent processing or evaluation was performed. In addition, examples in which large shrinkage cavities were observed in the shrinkage cavity evaluation of the airless ball were defined as unsuitable products, and no evaluations beyond that were performed. In addition, in the evaluation of ordinary bonding, the roundness and reliability evaluations of the narrow pitch bonding for the examples that were evaluated as "poor (×)" by 600-hour HAST or HTS were not performed. The bonding structure of Example 17 was also observed in the same manner. Figure 8 The EPMA image of Example 17 is shown in Fig. 9 An EPMA image of a bonding structure in which palladium is not present near the bonding surface is shown in FIG. It should be noted that the EPMA image can actually be obtained as a color photograph.

[0198]

[0199]

[0200]

[0201]

[0202]

[0203]

[0204] As shown in Tables 1 to 6, the palladium-coated copper bonding wire, which contains 1.0 to 4.0 mass % of palladium in the entire lead, contains sulfur, selenium, and tellurium in a predetermined concentration range, and has a palladium-rich region containing 6.5 to 30.0 atomic % of palladium on the surface of the free air ball after solidification, can suppress the generation of shrinkage cavities and has excellent reliability using HAST and HTS. <100> The orientation ratio is 15% or more, and <111> Orientation ratio is 50% or less ( <100> , <111> Any orientation includes an angle difference of less than 15° relative to the length direction of the lead) The palladium-coated copper bonding wire has extremely excellent roundness in the small-diameter ball, which can reduce short-circuit defects.

[0205] For example, in the above-mentioned vehicle-mounted equipment, the bonding life of the ball joint (first joint) formed by bonding the airless ball to the electrode has become the biggest problem. As far as vehicle-mounted equipment is concerned, it is required to be suitable for the resistance value of the semiconductor device that is ball-bonded with the aluminum electrode and sealed with resin after long-term exposure in HAST must be suppressed to a rise of less than 1.1 times before exposure. The halogen elements such as chlorine and moisture contained in the sealing resin implemented after the ball bonding have an adverse effect on the bonding life, that is, the increase in resistance value. These chlorine and moisture increase the resistance value of the joint by corroding the intermetallic compounds produced in the ball joint. The increase in resistance value will lead to poor power supply and hinder the transmission of electrical signals. Once it is used in a vehicle, it may also cause a car accident. As for the palladium-covered copper bonding wire of the above-mentioned embodiment, since the results of the HAST test are all good even after 600 hours of exposure, it is known that the bonding reliability is high, and even if it is used in vehicle-mounted equipment, it will not cause serious problems such as the above.

[0206] As shown in Table 6, the palladium-coated copper bonding wire having a gold layer had good evaluations of shrinkage cavities, HAST, and HTS as those of the palladium-coated copper bonding wire without a gold layer. This is believed to be because: the amount of gold derived from the gold layer was very small compared to the gold attached during the second bonding; and the gold covered the entire wire and did not locally aggregate, so shrinkage cavities were not caused.

[0207] <HAST test with severe specifications>

[0208] Next, the palladium-coated copper bonding wire of the specified example was evaluated for chip damage and a HAST test evaluation of severe specifications with the set temperature increased by 5°C and set at 135°C for 600 hours. The chip damage performance evaluation was performed by ball bonding under the same conditions as above using the palladium-coated copper bonding wire obtained in each example shown in Table 7, and observing the substrate directly below the ball bonding part with an optical microscope. 100 parts of the ball bonding part were observed. Example 17 was marked as good (○) because there was a small crack that was not a problem in use. The other examples were marked as excellent (◎) because no cracks occurred at all. In the HAST test of severe specifications, examples with a resistance value less than 1.1 times before the test were evaluated as ◎, and examples with a resistance of 1.1 to 1.2 times were evaluated as ○, as in the ordinary HAST test. It should be noted that in Example 1, the resistance value after the test in 5 circuits out of 500 circuits became 1.1 to 1.2 times that before the test, but all others were less than 1.1 times. In addition, as a comprehensive evaluation, the case where the results of both the chip damage evaluation and the severe specification HAST test were ◎ was evaluated as ◎, and the case where one of them was ○ and the other was ◎ was evaluated as ○. The results are shown in Table 7.

[0209]

[0210] From Table 7, it can be seen that Examples 2, 4, 11 to 15, and 17, in which the palladium concentration on the surface of the front end portion of the free air ball (palladium-rich region) is 7.0 atomic % or more, can withstand the test under the conditions that are more severe than usual, such as the temperature of the HAST test being set to 135°C. It is known that Example 1, in which the palladium concentration on the surface of the front end portion of the free air ball is 6.8 atomic %, has an example in which the resistance value becomes 1.1 to 1.2 times that after the test, which is slightly worse than the example in which the palladium concentration in the palladium-rich region is 7.0 atomic % or more. In addition, the example in which the palladium concentration on the surface of the front end portion of the free air ball is 23.0 atomic % or less does not even cause chip damage, and in Example 17 in which the palladium concentration exceeds 25.0 mass %, although there is no problem, chip damage occurs slightly. From these, it is known that the surface palladium concentration of the free air ball is preferably 7.0 atomic % to 25.0 atomic %. The palladium-coated copper bonding wire having a surface palladium concentration of 7.0 atomic % to 25.0 atomic % of the free air ball is suitable for vehicle-mounted devices and can also improve the yield.< / hkl> < / hkl> < / hkl> < / hkl> < / hkl> < / hkl> < / hkl>

Claims

1. A palladium-coated copper bonding wire comprising a core material having copper as a main component and a palladium layer on the core material and containing a chalcogenide element, The palladium-coated copper bonding wire contains 1.0 mass % to 4.0 mass % of palladium and 50 mass ppm or less of the total of the chalcogenide elements, and contains 5.0 mass ppm to 12.0 mass ppm of sulfur, 5.0 mass ppm to 20.0 mass ppm of selenium, or 15.0 mass ppm to 50.0 mass ppm of tellurium, relative to the total of copper, palladium, and chalcogenide elements. Crystal orientation in the lead length direction in the crystal plane of the cross section of the palladium-coated copper bonding wire <hkl> Among them, <100> The total of the orientation ratios is 15% or more, and <111> The orientation ratio is 50% or less, <100> and <111> The orientation includes an orientation with an angle difference of less than 15° relative to the length direction of the lead,< / hkl> When a free air ball is formed on the palladium-coated copper bonding wire, a palladium-rich region containing 6.5 atomic % to 30.0 atomic % of palladium relative to the total of copper and palladium is observed within a depth range of 5.0 nm to 100.0 nm from the surface of the front end portion of the free air ball.

2. The palladium-coated copper bonding wire according to claim 1, wherein The core material contains a total of 1 mass ppm to 3 mass % of one or more trace elements selected from P, Au, Pd, Pt, Ni, Ag, Rh, In, Ga and Fe based on the entire core material.

3. The palladium-coated copper bonding wire according to claim 1 or 2, wherein The core material comprises one or more trace elements selected from P, Au, Pd, Pt, Ni, Ag, Rh, In, Ga and Fe, and the core material contains: Containing 0.05 mass % to 3 mass % of the trace element of at least any one of Au, Pd, Pt, Ni and Rh; The trace element containing 0.01 mass % to 0.7 mass % of at least one of In and Ga; The trace element containing 5 to 500 ppm by mass of P; or The trace element of at least one of Ag and Fe is contained in an amount of 1 to 100 mass ppm.

4. The palladium-coated copper bonding wire according to any one of claims 1 to 3, wherein The palladium-coated copper bonding wire contains 1.0 mass % to 2.5 mass % of palladium derived from the palladium layer based on the total of copper, palladium, and chalcogenide elements.

5. The palladium-coated copper bonding wire according to any one of claims 1 to 4, wherein The palladium-coated copper bonding wire has a diameter of 10 μm to 25 μm.

6. The palladium-coated copper bonding wire according to any one of claims 1 to 5, wherein The free air ball was formed by applying a discharge current of 65 mA to the palladium-coated copper bonding wire in the presence of a mixed gas of nitrogen and hydrogen, and had a diameter 1.8 times the diameter of the palladium-coated copper bonding wire.

7. The palladium-coated copper bonding wire according to any one of claims 1 to 6, wherein The palladium concentration of the palladium-enriched region is determined by Auger electron spectroscopy under the following conditions: Acceleration voltage of primary electron beam: 10kV, Measurement area calculated from the set value: 15μm 2 ~20μm 2 , The acceleration voltage of argon ions for sputtering is 1 kV. Sputtering rate: 2.5 nm / min in terms of SiO2.

8. The palladium-coated copper bonding wire according to any one of claims 1 to 7, wherein A gold layer is provided on the palladium layer.

9. The palladium-coated copper bonding wire according to any one of claims 1 to 8, wherein The palladium-coated copper bonding wire contains 6.0 to 10.0 ppm by mass of sulfur (S) based on the entire wire.

10. The palladium-coated copper bonding wire according to any one of claims 1 to 9, wherein The palladium-coated copper bonding wire contains 6.0 mass ppm to 15.0 mass ppm of selenium (Se) based on the entire wire.

11. The palladium-coated copper bonding wire according to any one of claims 1 to 10, wherein The palladium-coated copper bonding wire contains 16.0 to 45.0 mass ppm of tellurium (Te) based on the entire wire.

12. A method for producing a palladium-coated copper bonding wire, which is a method for producing a palladium-coated copper bonding wire, The palladium-coated copper bonding wire has a core material having copper as a main component and a palladium layer on the core material and contains a chalcogen element. The palladium-coated copper bonding wire contains 1.0 mass % to 4.0 mass % of palladium and 50 mass ppm or less of the total of the chalcogenide elements, and contains 5.0 mass ppm to 12.0 mass ppm of sulfur, 5.0 mass ppm to 20.0 mass ppm of selenium, or 15.0 mass ppm to 50.0 mass ppm of tellurium, relative to the total of copper, palladium, and chalcogenide elements. The manufacturing method comprises the following steps: A process for preparing a copper wire material having copper as a main component; A step of forming a palladium layer containing the chalcogen element on the surface of the copper wire; The step of stretching the copper wire having the palladium layer formed thereon by 50% or more; and A step of performing heat treatment so that the elongation of the copper wire after the drawing becomes 5% to 15%.

13. A wire bonding structure comprising an electrode containing aluminum of a semiconductor chip, a bonding wire, and a ball bonding portion between the electrode and the bonding wire, The bonding wire is a palladium-coated copper bonding wire having a core material having copper as a main component and a palladium layer on the core material and containing a chalcogen element. The palladium-coated copper bonding wire contains 1.0 mass % to 4.0 mass % of palladium and 50 mass ppm or less of the total of the chalcogenide elements, and contains 5.0 mass ppm to 12.0 mass ppm of sulfur, 5.0 mass ppm to 20.0 mass ppm of selenium, or 15.0 mass ppm to 50.0 mass ppm of tellurium, relative to the total of copper, palladium, and chalcogenide elements. Crystal orientation in the lead length direction in the crystal plane of the cross section of the palladium-coated copper bonding wire <hkl> Among them, <100> The orientation ratio is 15% or more, and <111> The orientation ratio is 50% or less, <100> and <111> The orientation includes an orientation with an angle difference of less than 15° relative to the length direction of the lead,< / hkl> When a wire bonding structure is produced in which the palladium-coated copper bonding wire is ball-bonded to an aluminum electrode, a palladium-rich bonding region having a palladium concentration of 2 mass % or more relative to the total of aluminum, palladium and copper is provided near the bonding surface of the ball bond on the aluminum electrode.

14. The wire bonding structure according to claim 13, wherein: The palladium-enriched bonding region is disposed at least on a line parallel to the lead length direction and passing through a position that is one eighth of the distance from both ends of the maximum width of the ball bond.

15. The wire bonding structure according to claim 13 or 14, wherein: The occupancy rate of the palladium-enriched bonding region near the bonding surface is 25% or more.

16. A semiconductor device comprising a semiconductor chip, an aluminum electrode containing aluminum disposed on the semiconductor chip, an external electrode disposed outside the semiconductor chip and covered with gold or silver, and a bonding wire connecting the aluminum electrode to a surface of the external electrode, The bonding wire is made of palladium-coated copper wire, The wire bonding structure according to any one of claims 13 to 15 is provided in the vicinity of the bonding surface between the aluminum electrode and the bonding wire.

17. A semiconductor device comprising a semiconductor chip, an aluminum electrode containing aluminum disposed on the semiconductor chip, an external electrode disposed outside the semiconductor chip and covered with gold or silver, and a bonding wire connecting the aluminum electrode to a surface of the external electrode, The bonding wire is made of the palladium-coated copper bonding wire according to any one of claims 1 to 11.

18. The semiconductor device according to claim 16 or 17, wherein: The semiconductor device is a QFP (Quad Flat Packaging), a BGA (Ball grid array) or a QFN (Quad For Non-Lead Packaging).

19. The semiconductor device according to any one of claims 16 to 18, wherein: The semiconductor device is for vehicle use.

20. A method for manufacturing a semiconductor device, comprising: a semiconductor chip, an aluminum electrode disposed on the semiconductor chip and containing aluminum, an external electrode disposed outside the semiconductor chip and covered with gold or silver, and a bonding wire connecting the aluminum electrode to a surface of the external electrode, The bonding wire is a palladium-coated copper bonding wire having a core material having copper as a main component and a palladium layer on the core material and containing a chalcogen element. The palladium-coated copper bonding wire contains 1.0 mass % to 4.0 mass % of palladium and 50 mass ppm or less of the total of the chalcogenide elements, and contains 5.0 mass ppm to 12.0 mass ppm of sulfur, 5.0 mass ppm to 20.0 mass ppm of selenium, or 15.0 mass ppm to 50.0 mass ppm of tellurium, relative to the total of copper, palladium, and chalcogenide elements. Crystal orientation in the lead length direction in the crystal plane of the cross section of the palladium-coated copper bonding wire <hkl> Among them, <100> The total of the orientation ratios is 15% or more, and <111> The orientation ratio is 50% or less, <100> and <111> The orientation includes an orientation with an angle difference of less than 15° relative to the length direction of the lead,< / hkl> When a free air ball is formed on the palladium-coated copper bonding wire, a palladium-rich region containing 6.5 atomic % to 30.0 atomic % of palladium relative to the total of copper and palladium is observed within a range of 5.0 nm to 100.0 nm in the depth direction from the surface of the front end portion of the free air ball. The manufacturing method comprises the following steps: forming a free air ball at the front end of the palladium-coated copper bonding wire; A step of ball-bonding the palladium-coated copper bonding wire to the aluminum electrode using the free air ball; and and bonding a portion of the free air ball that is separated from the free air ball by a length of the palladium-coated copper bonding wire to the surface of the external electrode.

Citation Information

Patent Citations

  • Bonding structure of bonding wire, and method for forming the bonding structure

    JP2011146754A

  • Bonding wire

    JP2012156307A

  • Noble metal-coated copper wire for use in ball bonding

    JP2017092078A

  • Bonding wire for semiconductor device

    WO2016189758A1

  • Bonding wire for semiconductor

    CN102422404A